Adhesive composition

By adding thermally conductive filler to the thermally expandable structure epoxy adhesive, the peak core temperature problem caused by heat release is solved, and a more stable curing effect is achieved in large gap applications.

CN119790089APending Publication Date: 2025-04-08DDP SPECIALTY ELECTRONICS MATERIALS US LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380056735.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-02
Filing Date
2023-06-02
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The practicality of existing thermally expandable structural epoxy adhesives is limited in large gap applications, and due to the large amount of heat released during the open ring polymerization of the epoxide, the peak core temperature in the adhesive layer is too high, which in turn leads to thermal degradation of the adhesive.

Method used

The peak core temperature during curing is reduced by adding thermal fillers such as alumina, boron nitride, silicon nitride and graphite to the adhesive.

Benefits of technology

Effectively reduces peak core temperature during curing, reduces the risk of thermal degradation, and allows the adhesive to cure more stably in large gap applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005258141330000081
    Figure BDA0005258141330000081
  • Figure BDA0005258141330000091
    Figure BDA0005258141330000091
  • Figure BDA0005258141330000101
    Figure BDA0005258141330000101
Patent Text Reader

Abstract

Provided herein is an expandable epoxy adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of heat expandable adhesive compositions. Background Art

[0002] The current state-of-the-art in heat expandable adhesives for automotive metal bonding relies on expandable thermoplastics, epoxy and acrylic based tapes, and hot melt adhesives that aid in the sealing and reinforcement of cavities. Heat expandable structural epoxy adhesives offer excellent strength, water absorption characteristics, and metal adhesion as well as favorable processability for automotive assembly applications. However, the practicality of expandable structural epoxy adhesives in large gap applications is limited by the large amount of heat released during the ring-opening polymerization of the epoxide, which can result in peak core temperatures within the adhesive layer well above its cure temperature and ultimately thermal degradation of the adhesive.

[0003] There is a need for epoxy based structural adhesive pastes that can provide reduced peak core temperatures, thereby allowing them to be used in large gap applications. Summary of the invention

[0004] In a first aspect, the present invention provides an expandable adhesive composition comprising:

[0005] (A) at least one liquid epoxy resin;

[0006] (B) at least one blowing agent;

[0007] (C) at least one hardener;

[0008] (D) At least one thermally conductive filler.

[0009] In a second aspect, the present invention provides a method for bonding substrates, the method comprising the steps of:

[0010] (1) Providing an expandable adhesive composition, which comprises:

[0011] (A) at least one liquid epoxy resin;

[0012] (B) at least one blowing agent;

[0013] (C) at least one hardener;

[0014] (D) at least one thermally conductive filler;

[0015] (2) applying the expandable adhesive composition to the substrate;

[0016] (3) expanding the expandable adhesive composition; and

[0017] (4) Curing the expandable adhesive composition.

[0018] In a third aspect, the present invention provides a bonded assembly comprising substrates bonded with an adhesive produced by expansion and curing of an expandable adhesive composition comprising:

[0019] (A) at least one liquid epoxy resin;

[0020] (B) at least one blowing agent;

[0021] (C) at least one hardener;

[0022] (D) At least one thermally conductive filler. DETAILED DESCRIPTION

[0023] The inventors have discovered that expandable epoxy adhesives with reduced core temperatures during curing can be achieved by incorporating thermally conductive fillers. Such thermally expandable epoxy adhesive pastes can be robotically applied to oily automotive panels to fill and reinforce cavities during automated assembly processes, saving time and money. Specifically, thermally conductive fillers such as alumina, boron nitride, silicon nitride, and graphite were found to provide a significant reduction in the peak core temperature reached within the expandable epoxy resin paste during curing.

[0024] Definitions and Abbreviations

[0025] ATH Aluminum hydroxide, aluminum trihydrate

[0026] MDI 4,4'-methylenebis(phenyl isocyanate)

[0027] HDI Hexamethylene diisocyanate

[0028] HEMA Hydroxyethyl Methacrylate

[0029] IPDI Isophorone diisocyanate

[0030] PTMEG Poly(tetramethylene glycol)

[0031] PU Polyurethane

[0032] SEC Size Exclusion Chromatography

[0033] RH Relative humidity

[0034] CF Cohesive Failure

[0035] AF Bond Failure

[0036] M p Peak molecular weight, the molecular weight of the highest peak

[0037] FTIR Fourier Transform Infrared

[0038] PBT Poly(butylene terephthalate)

[0039] Equivalent weight and molecular weight are measured by gel permeation chromatography (GPC).

[0040] At least one liquid epoxy resin (A)

[0041] The adhesive of the invention comprises at least one liquid epoxy resin. The expression liquid epoxy resin comprises all epoxy resins which are flowable at 25°C, preferably having a viscosity of less than 1,500,000 mPa.s at 25°C when measured according to ASTM D-445.

[0042] In a preferred embodiment, the at least one epoxy resin comprises or consists of an epoxy resin having a viscosity at 25°C of less than 50,000 mPa.s, more preferably less than 20,000 mPa.s, when measured according to ASTM D-445.

[0043] Examples of suitable epoxy resins are those formed by the reaction of epichlorohydrin with bisphenols, particularly bisphenol A, bisphenol AP, bisphenol AF, bisphenol BP, bisphenol B, bisphenol C, bisphenol E, bisphenol F, bisphenol G, bisphenol M, bisphenol S, bisphenol P, bisphenol Z, and novolac epoxy resins (which are the reaction product of epichlorohydrin and novolac resins). Novolac resins are made from the reaction of phenol and formaldehyde, and epoxy resins are produced by the reaction of various glycols (other than bisphenols) with epichlorohydrin, such as dihexanediol diglycidyl ether.

[0044] Particularly preferred are epoxy resins produced by the reaction of epichlorohydrin and bisphenol A.

[0045] In particularly preferred embodiments, the at least one epoxy resin comprises or consists of an epoxy resin produced by the reaction of epichlorohydrin with bisphenol A and having a viscosity at 25°C of less than 50,000 mPa.s, more preferably less than 20,000 mPa.s when measured according to ASTM D-445.

[0046] In a preferred embodiment, the at least one liquid epoxy resin comprises a liquid reaction product of epichlorohydrin and bisphenol A, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445), and a functionality of 2.

[0047] The at least one liquid epoxy resin is preferably used in an amount of 10 to 65 wt %, more preferably 35 to 60 wt %, very particularly preferably 40 to 55 wt %, based on the total weight of the adhesive composition.

[0048] In a preferred embodiment, the at least one epoxy resin comprises or consists of an epoxy resin having a viscosity of less than 1,500,000 mPa.s at 25° C. when measured according to ASTM D-445, used in an amount of 10-65 wt %, more preferably 35-60 wt %, and more particularly preferably 40-55 wt %, based on the total weight of the adhesive composition.

[0049] In a preferred embodiment, the at least one epoxy resin comprises or consists of an epoxy resin having a viscosity of less than 50,000 mPa.s, more preferably less than 20,000 mPa.s at 25° C. when measured according to ASTM D-445, and is used in an amount of 10-65 wt %, more preferably 35-60 wt %, and more particularly preferably 40-55 wt %, based on the total weight of the adhesive composition.

[0050] In another preferred embodiment, the at least one epoxy resin comprises or consists of an epoxy resin formed by the reaction of epichlorohydrin with bisphenol, in particular bisphenol A, bisphenol AP, bisphenol AF, bisphenol BP, bisphenol B, bisphenol C, bisphenol E, bisphenol F, bisphenol G, bisphenol M, bisphenol S, bisphenol P, bisphenol Z, and is used in an amount of 10-65 wt %, more preferably 35-60 wt %, and more preferably 40-55 wt %, based on the total weight of the adhesive composition.

[0051] In another preferred embodiment, the at least one epoxy resin comprises or consists of an epoxy resin produced by the reaction of epichlorohydrin with bisphenol A, used in an amount of 10-65 wt %, more preferably 35-60 wt %, and more particularly preferably 40-55 wt %, based on the total weight of the adhesive composition.

[0052] In another preferred embodiment, the at least one epoxy resin comprises or consists of an epoxy resin produced by the reaction of epichlorohydrin with bisphenol A and having a viscosity of less than 50,000 mPa.s, more preferably less than 20,000 mPa.s at 25° C. when measured according to ASTM D-445, and is used in an amount of 10-65 wt %, more preferably 35-60 wt %, and more particularly preferably 40-55 wt %, based on the total weight of the adhesive composition.

[0053] In another embodiment, the at least one liquid epoxy resin comprises a liquid reaction product of epichlorohydrin and bisphenol A, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445) and a functionality of 2, and is used in an amount of 10-65 wt %, more preferably 35-60 wt %, and more particularly preferably 40-55 wt %, based on the total weight of the adhesive composition.

[0054] At least one blowing agent (B)

[0055] The adhesive composition of the present invention comprises at least one blowing agent.

[0056] The blowing agent is preferably selected from physical blowing agents, which are low boiling point molecules or entrapped or encapsulated gases, and chemical blowing agents, which are molecules that decompose during curing to release gases.

[0057] Suitable physical blowing agents consist of expandable graphite, and gases (e.g. hydrocarbons such as butane, pentane) and low boiling point molecules such as water, nitrogen, carbon dioxide, propane, butane and pentane) encapsulated in a polymer shell such as poly(acrylonitrile) or acrylate copolymers.

[0058] Suitable chemical blowing agents include

[0059] 1. Isocyanate

[0060] 2. Azo compounds (e.g. azobisisobutyronitrile, diisopropyl azodicarboxylate, azodicarbonamide)

[0061] 3. Hydrazine derivatives [e.g. 4,4'-oxybis(benzenesulfonylhydrazide), p-toluenesulfonylhydrazide]

[0062] 4. Semicarbazide and sulfonyl semicarbazide [e.g. p-toluenesulfonyl semicarbazide, 4,4'-oxybis(benzenesulfonyl semicarbazide), p,p-oxybisbenzenesulfonyl hydrazide]

[0063] 5. N-nitroso compounds (e.g. dinitrosopentamethylenetetramine)

[0064] 6. Tetrazoles (e.g. 5-phenyltetrazole, 5-aminotetrazole)

[0065] 7. Poly(siloxane)

[0066] 8. Salts of carbonic acid and polycarboxylic acids (e.g. sodium bicarbonate)

[0067] 9. Peroxides (eg peroxycaproate, peroxydicarbonate).

[0068] In a preferred embodiment, the blowing agent comprises or consists of a physical blowing agent, more preferably a hydrocarbon gas encapsulated in a polymer, in particular isooctane, isobutane or isopentane encapsulated in an acrylonitrile copolymer.

[0069] In another preferred embodiment, the blowing agent comprises or consists of a chemical blowing agent, in particular an azo compound, more particularly azodicarbonamide.

[0070] In another preferred embodiment, the blowing agent is a mixture of a physical blowing agent and a chemical blowing agent, such as a mixture of isooctane, isobutane or isopentane and azodicarbonamide encapsulated in an acrylonitrile copolymer.

[0071] The blowing agent is preferably used in an amount of 0.25 to 10 wt %, more preferably 0.5 to 5 wt %, very particularly preferably 0.75 to 1.5 wt %, based on the total weight of the adhesive composition.

[0072] In a preferred embodiment, the blowing agent is selected from physical blowing agents, which are low boiling point molecules or trapped or encapsulated gases, and chemical blowing agents, which are molecules that decompose to release gas during curing, and is used in an amount of 0.25-2.35 wt%, more preferably 0.5-2.15 wt%, and more particularly preferably 0.75-1.5 wt%, based on the total weight of the adhesive composition.

[0073] In another preferred embodiment, the blowing agent is a physical blowing agent selected from expandable graphite, a gas (e.g. hydrocarbons, such as butane, pentane) encapsulated in a polymer shell such as an acrylate copolymer or poly(acrylonitrile) and low boiling point molecules such as water, nitrogen, carbon dioxide, propane, butane and pentane, used in an amount of 0.25-2.35 wt%, more preferably 0.5-2.15 wt%, more particularly preferably 0.75-1.5 wt%, based on the total weight of the adhesive composition.

[0074] In another preferred embodiment, the blowing agent is selected from the following chemical blowing agents:

[0075] 1. Isocyanate

[0076] 2. Azo compounds (e.g. azobisisobutyronitrile, diisopropyl azodicarboxylate, azodicarbonamide)

[0077] 3. Hydrazine derivatives [e.g. 4,4'-oxybis(benzenesulfonylhydrazide), p-toluenesulfonylhydrazide]

[0078] 4. Semicarbazide and sulfonyl semicarbazide [e.g. p-toluenesulfonyl semicarbazide, 4,4'-oxybis(benzenesulfonyl semicarbazide), p,p-oxybisbenzenesulfonyl hydrazide]

[0079] 5. N-nitroso compounds (e.g. dinitrosopentamethylenetetramine)

[0080] 6. Tetrazoles (e.g. 5-phenyltetrazole, 5-aminotetrazole)

[0081] 7. Poly(siloxane)

[0082] 8. Salts of carbonic acid and polycarboxylic acids (e.g. sodium bicarbonate)

[0083] 9. Peroxides (e.g. peroxycaproate, peroxydicarbonate),

[0084] The amount used is 0.25-2.35 wt %, more preferably 0.5-2.15 wt %, and even more preferably 0.75-1.5 wt %, based on the total weight of the adhesive composition.

[0085] In another preferred embodiment, the blowing agent is a physical blowing agent, more preferably a hydrocarbon gas encapsulated in a polymer, in particular isopropane, isobutane or isopentane encapsulated in an acrylic copolymer or polyacrylonitrile, used in an amount of 0.25-2.35 wt%, more preferably 0.5-2.15 wt%, and more particularly preferably 0.75-1.5 wt%, based on the total weight of the adhesive composition.

[0086] In another preferred embodiment, the blowing agent is a mixture of a physical blowing agent and a chemical blowing agent, such as a mixture of isooctane, isobutane or isopentane and azodicarbonamide encapsulated in acrylonitrile, wherein the physical blowing agent is used at 0.2-1 wt% and the chemical blowing agent is used at 0.2-1 wt% based on the total weight of the mixed adhesive.

[0087] In a particularly preferred embodiment, the blowing agent is 0.4-0.8 wt% isooctane, isobutane or isopentane encapsulated in acrylonitrile and 0.3-0.7 wt% azodicarbonamide.

[0088] At least one hardener (C)

[0089] The adhesive composition of the present invention comprises at least one hardener.

[0090] For one-component adhesives, the hardener is preferably a latent hardener, which means a hardener that is activated when exposed to heat. Examples of latent hardeners include dicyandiamide, hydrazide and anhydride hardeners. Particularly preferred is dicyandiamide.

[0091] Examples of suitable anhydrides include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methyl-5-norbornene-2,3-dicarboxylic anhydride, alkenyl succinic anhydride (eg, dodecenyl succinic anhydride), and trimellitic anhydride.

[0092] Examples of suitable hydrazides include adipic acid dihydrazide, sebacic acid dihydrazide, dodecane dihydrazide, isophthalic acid dihydrazide, and salicylic acid dihydrazide.

[0093] For two-part adhesives in which the epoxy component and the hardener component are mixed immediately prior to use, the hardener may be latent as described above, or it may be a non-latent hardener. Examples of non-latent hardeners include polyamines, substituted triazines, imidazoles, polycarboxylic acids, polyols, and polyamides.

[0094] Examples of suitable polyamines include aliphatic polyamines, alicyclic polyamines, aromatic polyamines, polyether-based polyamines, polyethyleneimines, and polyamine derivatives.

[0095] Examples of the aliphatic polyamines include diethylenetriamine, triethylenetetramine (TETA), triethylenediamine, tetraethylenepentamine, dipropylenediamine, diethylaminopropylamine, N-aminoethylpiperazine, menthanediamine, isophoronediamine, and derivatives of these polyamines.

[0096] Examples of polyether-based polyamines include those based on poly(propylene oxide), such as those having the following structure:

[0097]

[0098] In a preferred embodiment, the hardener is a latent hardener.

[0099] In another preferred embodiment, the hardener is dicyandiamide.

[0100] In another preferred embodiment, the hardener is a latent hardener, which is used in an amount of 0.5-8 wt %, more preferably 1-6 wt %, particularly preferably 3-5 wt %, based on the total weight of the adhesive composition.

[0101] In another preferred embodiment, the hardener is selected from dicyandiamide, hydrazine and anhydride hardeners, and is used in an amount of 0.5-8 wt %, more preferably 1-6 wt %, particularly preferably 3-5 wt %, based on the total weight of the adhesive composition.

[0102] In another preferred embodiment, the hardener is dicyandiamide, which is used in an amount of 0.5-8 wt %, more preferably 1-6 wt %, particularly preferably 3-5 wt %, based on the total weight of the adhesive composition.

[0103] In another preferred embodiment, the hardener is a non-latent hardener selected from the group consisting of polyamines, polyamides, substituted triazines, imidazoles, polycarboxylic acids and polyols, used in an amount of 0.5-50 wt %, more preferably 20-50 wt %, particularly preferably 30-50 wt %. In the case of two-component (2K) adhesives, these concentrations refer to the adhesive mixture resulting from mixing the epoxy component and the hardener component.

[0104] Examples of suitable polyamines include aliphatic polyamines, cycloaliphatic polyamines, aromatic polyamines, polyether-based polyamines, polyethyleneimines, which are used in an amount of 0.5-50 wt %, more preferably 20-50 wt %, particularly preferably 30-50 wt %. In the case of two-component (2K) adhesives, these concentrations refer to the adhesive mixture resulting from mixing the epoxy component and the hardener component.

[0105] Examples of aliphatic polyamines include diethylenetriamine, triethylenetetramine (TETA), triethylenediamine, tetraethylenepentamine, dipropylenediamine, diethylaminopropylamine, N-aminoethylpiperazine, menthanediamine, isophoronediamine, which are used in an amount of 0.5-50 wt %, more preferably 20-50 wt %, particularly preferably 30-50 wt %. In the case of two-component (2K) adhesives, these concentrations refer to the adhesive mixture resulting from mixing the epoxy component and the hardener component.

[0106] Examples of polyether-based polyamines include those based on poly(propylene oxide), such as those having the following structure:

[0107]

[0108]

[0109] These polyamines are used at 0.5-50 wt %, more preferably 20-50 wt %, particularly preferably 30-50 wt %. In the case of two-component (2K) adhesives, these concentrations refer to the adhesive mixture resulting from mixing the epoxy component and the hardener component.

[0110] At least one thermally conductive filler (D)

[0111] Thermally conductive fillers are not particularly limited. Suitable thermally conductive fillers are those having a thermal conductivity greater than 5 W / m°K, greater than 10 W / m°K, or greater than 15 W / m°K. Examples of thermally conductive fillers include alumina, alumina trihydrate or aluminum hydroxide (ATH), silicon carbide, boron nitride, diamond, and graphite, and mixtures thereof. Particularly preferred are aluminum hydroxide (ATH) and aluminum oxide, with ATH being the most preferred. Also preferred are mixtures of ATH and aluminum oxide, particularly mixtures having a wt:wt ratio of ATH:alumina of 8-15. The thermally conductive filler may be surface treated or untreated.

[0112] In a preferred embodiment, the thermally conductive filler has a broad particle size distribution characterized by a D90 / D50 ratio of 3 or about 3 or more. Particularly preferably, the thermally conductive filler is ATH or alumina having a broad particle size distribution characterized by a D90 / D50 ratio of 3 or about 3 or more, most preferably ATH.

[0113] Also preferred are thermally conductive fillers having a bimodal particle size distribution. A bimodal distribution is when, for example, the D90 / D50 ratio is 3 or about 3 or more, more preferably 5 or about 5 or more, more particularly preferably 9 or about 9 or more. For example, the particles have a D50 of 5 to 20 microns and a D90 of 70 to 90 microns, particularly a D50 of 7-9 microns and a D90 of 78-82 microns. The particle size can be determined using laser diffraction. For ATH, a suitable solvent is deionized water containing a dispersing aid such as Na4P2O7 x 10H2O, preferably containing the dispersing aid at 1 g / l. Preferred are alumina and ATH having a bimodal distribution, particularly ATH. In a preferred embodiment, the thermally conductive filler is ATH having a D90 / D50 of 3 or about 3 or more, more preferably 5 or about 5 or more, particularly preferably 9 or about 9 or more.

[0114] In a preferred embodiment, the thermally conductive filler is a bimodal aluminum hydroxide (ATH) having the following particle size distribution (by laser diffraction in deionized water containing a dispersing aid such as Na4P2O7 x 10H2O, preferably containing the dispersing aid at 1 g / l):

[0115] D 10 (micrometer) 0.5

[0116] D 50 (micrometer)8

[0117] D 90 (micrometers)80.

[0118] The thermally conductive filler is preferably present in the adhesive in a concentration of 10 to 55 wt %, more preferably 15 to 45 wt %, very particularly preferably 20 to 42 wt %, based on the total weight of the finished adhesive. In the case of two-component (2K) adhesives, these concentrations refer to the adhesive mixture resulting from mixing the epoxy component and the hardener component.

[0119] In a preferred embodiment, the thermally conductive filler is aluminum hydroxide (ATH), which is used in a concentration of 10-55 wt %, more preferably 15-45 wt %, and very particularly preferably 20-42 wt %, based on the total weight of the adhesive. In the case of a two-component (2K) adhesive, these concentrations refer to the adhesive mixture resulting from mixing the epoxy component and the hardener component.

[0120] In a preferred embodiment, the thermally conductive filler is aluminum hydroxide (ATH) having the following particle size distribution (by laser diffraction in deionized water containing a dispersing aid such as Na4P2O7 x 10H2O, preferably containing the dispersing aid at 1 g / l):

[0121] D 10 (micrometer) 0.5

[0122] D 50 (micrometer)8

[0123] D 90 (micrometer)80

[0124] The thermally conductive filler is used in a concentration of 10-55 wt %, more preferably 15-45 wt %, very particularly preferably 20-42 wt %, based on the total weight of the adhesive. In the case of two-component (2K) adhesives, these concentrations refer to the adhesive mixture resulting from mixing the epoxy component and the hardener component.

[0125] Optional Ingredients

[0126] The adhesive of the present invention may contain additional optional ingredients such as, for example:

[0127] 1. One or more toughening agents: Toughening agents are elastomeric molecules that are compatible with the epoxy matrix and impart impact resistance and elasticity to the hardened adhesive. Examples include polyurethane-based toughening agents, rubber-based toughening agents, core-shell rubber toughening agents. In a preferred embodiment, the at least one toughening agent is selected from those molecules with terminal functional groups that can react with the epoxy matrix during polymerization. Suitable toughening agents include polyurethane-based toughening agents in which the terminal NCO group is uncapped or capped (e.g., with a phenol or polyphenol), polybutadiene-based toughening agents capped with amine or diol functional groups. In a preferred embodiment, the at least one toughening agent is selected from polyurethane toughening agents, particularly those in which the terminal NCO group is capped with a phenolic group, particularly cardanol.

[0128] In a particularly preferred embodiment, the at least one toughening agent is prepared by reacting a polybutadiene diol, a polyether diol and a diisocyanate so that the resulting molecule carries a terminal NCO group. This toughening agent can be used as is, or it can be end-capped with a phenol or polyphenol. In a preferred embodiment, it is end-capped with cardanol.

[0129] If used, the at least one toughening agent is preferably used at 3 to 25 wt%, more preferably 12 to 18 wt%, based on the total weight of the adhesive.

[0130] In a preferred embodiment, the toughening agent is selected from polyurethane-based toughening agents, rubber-based toughening agents and core-shell rubber toughening agents, and is used at 3-25 wt%, more preferably 12-18 wt%, based on the total weight of the adhesive.

[0131] In another preferred embodiment, the at least one toughening agent is selected from those molecules with terminal functional groups that can react with the epoxy matrix during polymerization, used at 3-25 wt%, more preferably 12-18 wt%, based on the total weight of the adhesive.

[0132] In another preferred embodiment, the at least one toughening agent is selected from polyurethane-based toughening agents in which the terminal NCO group is uncapped or capped (e.g., capped with phenol or polyphenol), polybutadiene-based toughening agents capped with amine or diol functional groups, and is used in an amount of 3-25 wt%, more preferably 12-18 wt%, based on the total weight of the adhesive.

[0133] In another preferred embodiment, the at least one toughening agent is selected from polyurethane toughening agents in which the terminal NCO groups are capped with phenolic groups, especially cardanol, and is used at 3-25 wt%, more preferably 12-18 wt%, based on the total weight of the adhesive.

[0134] In a particularly preferred embodiment, the at least one toughening agent is prepared by reacting polybutadiene diol, polyether diol and diisocyanate so that the resulting molecule carries terminal NCO groups and is used at 3-25 wt%, more preferably 12-18 wt%, based on the total weight of the adhesive.

[0135] In another particularly preferred embodiment, the at least one toughening agent is prepared by reacting polybutadiene diol, polyether diol and diisocyanate so that the resulting molecule has a terminal NCO group, followed by end-capping with cardanol, and is used in an amount of 3-25 wt%, more preferably 12-18 wt%, based on the total weight of the adhesive.

[0136] 2. One or more silane adhesion promoters: The adhesive composition of the present invention may include one or more silane adhesion promoters.

[0137] Preferred silane adhesion promoters have the general formula I:

[0138]

[0139] Where R 1 , R 2 and R 3 are independently selected from C1-C4-alkyl, R 2 is a divalent C2-C6-alkylene group, and W is a glycidyl group, an amino group or a mercapto group.

[0140] In a preferred embodiment, in Formula I, W is glycidyl.

[0141] In another preferred embodiment, in Formula I, R 1 , R 2 and R 3 is methyl and R 2 It is propylene.

[0142] In another preferred embodiment, in Formula I, R 1 , R 2 and R 3 is methyl, R 2 is propylene, and W is glycidyl.

[0143] In a preferred embodiment, the adhesive composition of the present invention comprises γ-glycidylpropyltrimethoxysilane.

[0144] When used, the silane adhesion promoter is preferably present at 0.05 to 1 wt %, more preferably 0.1 to 0.75 wt %, and even more preferably 0.2 to 0.4 wt %, based on the total weight of the adhesive composition.

[0145] Preferably, the at least one silane adhesion promoter has the general formula I:

[0146]

[0147] Where R 1 , R 2 and R 3 are independently selected from C1-C4-alkyl, R 2 W is a divalent C2-C6-alkylene group, and W is a glycidyl group, an amino group or a mercapto group, and the silane adhesion promoter is used in an amount of 0.05-1 wt %, more preferably 0.1-0.75 wt %, and more preferably 0.2-0.4 wt %, based on the total weight of the adhesive composition.

[0148] In a preferred embodiment, in formula I, W is a glycidyl group, and the adhesion promoter is used at 0.05-1 wt %, more preferably 0.1-0.75 wt %, and more particularly preferably 0.2-0.4 wt %, based on the total weight of the adhesive composition.

[0149] In another preferred embodiment, in Formula I, R 1 , R 2 and R 3 is methyl and R 2 The adhesion promoter is propylene, and is used in an amount of 0.05-1 wt %, more preferably 0.1-0.75 wt %, and more particularly preferably 0.2-0.4 wt %, based on the total weight of the adhesive composition.

[0150] In another preferred embodiment, in Formula I, R 1 , R 2 and R 3 is methyl, R 2 is propylene, and W is glycidyl, and the adhesion promoter is used in an amount of 0.05-1 wt %, more preferably 0.1-0.75 wt %, and more particularly preferably 0.2-0.4 wt %, based on the total weight of the adhesive composition.

[0151] In a preferred embodiment, the adhesive composition of the present invention comprises γ-glycidylpropyltrimethoxysilane, which is used in an amount of 0.05-1 wt %, more preferably 0.1-0.75 wt %, and more preferably 0.2-0.4 wt %, based on the total weight of the adhesive composition.

[0152] 3. One or more epoxide polymerization catalysts: The adhesive composition of the present invention may optionally contain one or more epoxide polymerization catalysts.

[0153] The epoxy polymerization catalyst may be a Lewis base or a Lewis acid. Examples of Lewis bases include tertiary amines and imidazoles.

[0154] Examples of Lewis acids include BF3, ZnCl2, SnCl4, FeCl3, AlCl3, boron trifluoride complexes.

[0155] In a preferred embodiment, the catalyst is a Lewis base, more preferably a tertiary amine.

[0156] Examples of suitable tertiary amines include 2,4,6-tris(dimethylaminomethyl)phenol, tetramethylguanidine, heptamethylisobiguanide, N,N-dimethylbenzylamine.

[0157] In another preferred embodiment, the catalyst is 2,4,6-tris(dimethylaminomethyl)phenol, in particular 2,4,6-tris(dimethylaminomethyl)phenol on a novolac support.

[0158] For two-component adhesives comprising an epoxy component and a hardener component, a catalyst is formulated with the hardener component.

[0159] The catalyst is preferably used in an amount of 0.25-1.2 wt%, more preferably 0.5-1 wt%, based on the total weight of the adhesive composition.

[0160] In a preferred embodiment, the catalyst is a Lewis base, used at 0.25-1.2 wt%, more preferably 0.5-1 wt%, based on the total weight of the adhesive composition.

[0161] In a preferred embodiment, the catalyst is a Lewis acid, used at 0.25-1.2 wt%, more preferably 0.5-1 wt%, based on the total weight of the adhesive composition.

[0162] In another preferred embodiment, the catalyst is selected from tertiary amines and imidazoles, and is used in an amount of 0.25-1.2 wt %, more preferably 0.5-1 wt %, based on the total weight of the adhesive composition.

[0163] In another preferred embodiment, the catalyst is selected from BF3, ZnCl2, SnCl4, FeCl3, AlCl3 and boron trifluoride complexes, and is used in an amount of 0.25-1.2 wt%, more preferably 0.5-1 wt%, based on the total weight of the adhesive composition.

[0164] In another preferred embodiment, the catalyst is a tertiary amine, used at 0.25-1.2 wt%, more preferably 0.5-1 wt%, based on the total weight of the adhesive composition.

[0165] In another preferred embodiment, the catalyst is selected from 2,4,6-tris(dimethylaminomethyl)phenol, tetramethylguanidine, heptamethylisobiguanide, N,N-dimethylbenzylamine, and is used in an amount of 0.25-1.2 wt %, more preferably 0.5-1 wt %, based on the total weight of the adhesive composition.

[0166] In another preferred embodiment, the catalyst is 2,4,6-tris(dimethylaminomethyl)phenol, especially 2,4,6-tris(dimethylaminomethyl)phenol on a novolac carrier, used at 0.25-1.2 wt%, more preferably 0.5-1 wt%, based on the total weight of the adhesive composition.

[0167] 4. One or more thermoplastic polymers: The adhesive of the present invention preferably comprises one or more thermoplastic polymers.

[0168] In a preferred embodiment, the one or more thermoplastic polymers are in the form of a powder, in particular a powder having an average particle size of less than 60 μm.

[0169] Examples of suitable thermoplastics include polyamides, polyesters and copolyetheresters, preferably in powder form.

[0170] In a preferred embodiment, the adhesive composition comprises a polyamide, in particular a long-chain polyamide. Suitable long-chain polyamides include those made from diacids, diamines or lactams or amino-carboxylic acids having 6 to 12 carbon atoms, preferably in powder form. Examples include PA66, PA6, PA11, PA12, PA410, PA610, PA1010, PA612, PA1212, preferably in powder form.

[0171] In a particularly preferred embodiment, the adhesive composition comprises a polyamide selected from the group consisting of PA12, preferably in powder form, PA11, PA610, PA1010, PA612, PA1212, and mixtures of these, wherein PA12, preferably in powder form, is particularly preferred.

[0172] In a preferred embodiment, the adhesive composition comprises a copolyetherester, preferably in powder form, in particular a copolyetherester comprising a PBT hard segment and a PTMEG soft segment, preferably in powder form.

[0173] In a preferred embodiment, the adhesive composition comprises polyester, preferably in powder form, in particular PBT, preferably in powder form.

[0174] For two-component adhesive compositions (2K) comprising an epoxy component and a hardener component, thermoplastics may be mixed with either component or both.

[0175] If used, thermoplastics are preferably used at 5-30 wt %, more preferably 7-22 wt %, particularly preferably 8-15 wt %, based on the total weight of the adhesive composition.

[0176] In a preferred embodiment, the one or more thermoplastic polymers are in the form of a powder, especially a powder with an average particle size of less than 60 μm, and are used in an amount of 5-30 wt%, more preferably 7-22 wt%, particularly preferably 8-15 wt%, based on the total weight of the adhesive composition.

[0177] In another preferred embodiment, the thermoplastic is selected from polyamides, polyesters and copolyetheresters, preferably in powder form, and is used in an amount of 5-30 wt %, more preferably 7-22 wt %, particularly preferably 8-15 wt %, based on the total weight of the adhesive composition.

[0178] In another preferred embodiment, the adhesive composition comprises a polyamide, preferably in powder form, in particular a polyamide made from a diacid, diamine or lactam or amino-carboxylic acid having 6 to 12 carbon atoms, which is used in an amount of 5 to 30 wt %, more preferably 7 to 22 wt %, particularly preferably 8 to 15 wt %, based on the total weight of the adhesive composition.

[0179] In another preferred embodiment, the thermoplastic is selected from PA66, PA6, PA11, PA12, PA410, PA610, PA1010, PA612, PA1212, preferably in powder form, and is used in an amount of 5-30 wt%, more preferably 7-22 wt%, particularly preferably 8-15 wt%, based on the total weight of the adhesive composition.

[0180] In another preferred embodiment, the thermoplastic is selected from PA12, PA11, PA610, PA1010, PA612, PA1212 and mixtures of these, preferably in powder form, and is used in an amount of 5-30 wt%, more preferably 7-22 wt%, particularly preferably 8-15 wt%, based on the total weight of the adhesive composition.

[0181] In another preferred embodiment, the thermoplastic is selected from PA12, preferably in powder form, used in an amount of 5-30 wt %, more preferably 7-22 wt %, particularly preferably 8-15 wt %, based on the total weight of the adhesive composition.

[0182] In another preferred embodiment, the adhesive composition comprises the copolyetherester, preferably in powder form, used in an amount of 5-30 wt %, more preferably 7-22 wt %, particularly preferably 8-15 wt %, based on the total weight of the adhesive composition.

[0183] In another preferred embodiment, the adhesive composition comprises a copolyetherester selected from those comprising a PBT hard segment and a PTMEG soft segment, preferably in powder form, which is used in an amount of 5-30 wt%, more preferably 7-22 wt%, particularly preferably 8-15 wt%, based on the total weight of the adhesive composition.

[0184] In another preferred embodiment, the adhesive composition comprises the polyester, preferably in powder form, which is used in an amount of 5-30 wt %, more preferably 7-22 wt %, particularly preferably 8-15 wt %, based on the total weight of the adhesive composition.

[0185] In another preferred embodiment, the adhesive composition comprises PBT, preferably in powder form, which is used in an amount of 5-30 wt %, more preferably 7-22 wt %, particularly preferably 8-15 wt %, based on the total weight of the adhesive composition.

[0186] 5. Non-thermally conductive fillers: The adhesive composition of the present invention may optionally contain non-thermally conductive fillers, such as, for example, calcium carbonate, fumed silica, clay.

[0187] Manufacturing method

[0188] For one-component adhesives (1K), simply mix the ingredients together until homogeneous.

[0189] In a preferred method of manufacture, the epoxy component, silane adhesion promoter (if used), and toughening agent (if used) are mixed together until substantially homogeneous. Thermally conductive fillers and other fillers (if used) are added and mixed. A blowing agent is added, and an epoxy polymerization catalyst (if used) and a hardener are added, and the mixture is mixed until homogeneous.

[0190] For a two-component adhesive, the epoxy component, silane adhesion promoter (if used), and toughening agent (if used) are mixed together until substantially homogeneous. Thermally conductive fillers and other fillers (if used) are added and mixed. This mixture forms the first component (epoxy component). The hardener, epoxy polymerization catalyst (if used), blowing agent, and thermally conductive fillers and other fillers (if used) are mixed until homogeneous to form the second component (hardener component).

[0191] How to use

[0192] The present invention also provides a method for bonding substrates, the method comprising the following steps:

[0193] (1) Providing an expandable adhesive composition, which comprises:

[0194] (A) at least one liquid epoxy resin;

[0195] (B) at least one blowing agent;

[0196] (C) at least one hardener;

[0197] (D) at least one thermally conductive filler;

[0198] (2) applying the expandable adhesive composition to the substrate;

[0199] (3) expanding the expandable adhesive composition; and

[0200] (4) Curing the expandable adhesive composition.

[0201] The adhesive may be applied to the substrate by any method including spreading and applying through a nozzle, with application through a nozzle being particularly preferred.

[0202] The expansion is typically carried out by heating, which also initiates the curing of the adhesive. The heating may be carried out using any heating method, such as an oven, IR radiation or RF radiation.

[0203] Heating is preferably carried out to at least 120° C. Heating may be to 150° C., 160° C., 170° C. or 180° C. Curing of epoxy resins is exothermic, so once curing has begun, heating may no longer be necessary.

[0204] Effects of the Invention

[0205] The adhesives of the present invention exhibit reduced 12 mm peak core temperatures compared to adhesives that do not include thermally conductive fillers and / or compared to adhesives that do not include thermoplastic polymers, when measured using the method set forth in the Examples.

[0206] Preferably, the adhesive composition of the present invention exhibits a 12 mm peak core temperature of 275°C or less, more preferably 260°C or less, when measured using the method listed in the Examples.

[0207] The adhesive composition of the present invention preferably exhibits an expansion percentage of 130% or more.

[0208] In preferred embodiments, the adhesive composition of the present invention exhibits a 12 mm peak core temperature of 275° C. or less, more preferably 260° C. or less, and a percent expansion of 130% or greater when measured using the methods listed in the Examples.

[0209] application

[0210] The adhesives of the present invention are particularly suitable for bonding metal substrates and filling cavities in automotive body shops to produce robust composite assemblies.

[0211] Particularly preferred embodiments

[0212] The following are particularly preferred embodiments of the present invention:

[0213] 1. An expandable adhesive composition comprising:

[0214] (A) at least one liquid epoxy resin;

[0215] (B) at least one blowing agent;

[0216] (C) at least one hardener;

[0217] (D) At least one thermally conductive filler.

[0218] 2. A method for bonding substrates, the method comprising the following steps:

[0219] (1) Providing an expandable adhesive composition, which comprises:

[0220] (A) at least one liquid epoxy resin;

[0221] (B) at least one blowing agent;

[0222] (C) at least one hardener;

[0223] (D) at least one thermally conductive filler;

[0224] (2) applying the expandable adhesive composition to the substrate;

[0225] (3) expanding the expandable adhesive composition; and

[0226] (4) Curing the expandable adhesive composition.

[0227] 3. A bonded assembly comprising substrates bonded with an adhesive produced by expansion and curing of an expandable adhesive composition comprising:

[0228] (A) at least one liquid epoxy resin;

[0229] (B) at least one blowing agent;

[0230] (C) at least one hardener;

[0231] (D) At least one thermally conductive filler.

[0232] 4. An expandable adhesive composition comprising:

[0233] (A) at least one liquid epoxy resin;

[0234] (B) at least one blowing agent;

[0235] (C) at least one hardener;

[0236] (D) at least one thermally conductive filler;

[0237] (E) at least one thermoplastic polymer.

[0238] 5. A method for bonding substrates, the method comprising the steps of:

[0239] (1) Providing an expandable adhesive composition, which comprises:

[0240] (A) at least one liquid epoxy resin;

[0241] (B) at least one blowing agent;

[0242] (C) at least one hardener;

[0243] (D) at least one thermally conductive filler;

[0244] (E) at least one thermoplastic polymer;

[0245] (2) applying the expandable adhesive composition to the substrate;

[0246] (3) expanding the expandable adhesive composition; and

[0247] (4) Curing the expandable adhesive composition.

[0248] 6. A bonded assembly comprising substrates bonded with an adhesive produced by expansion and curing of an expandable adhesive composition comprising:

[0249] (A) at least one liquid epoxy resin;

[0250] (B) at least one blowing agent;

[0251] (C) at least one hardener;

[0252] (D) at least one thermally conductive filler;

[0253] (E) at least one thermoplastic polymer.

[0254] 7. As described in any preceding embodiment, wherein the liquid epoxy resin includes all epoxy resins that are flowable at 25°C, preferably having a viscosity of less than 1,500,000 mPas at 25°C when measured according to ASTM D-445.

[0255] 8. As described in any preceding embodiment, wherein the at least one epoxy resin comprises or consists of an epoxy resin having a viscosity at 25° C. of less than 50,000 mPa.s, more preferably less than 20,000 mPa.s, when measured according to ASTM D-445.

[0256] 9. As described in any of the preceding embodiments, the epoxy resin comprises or consists of an epoxy resin selected from those formed by the reaction of epichlorohydrin and bisphenols, particularly bisphenol A, bisphenol AP, bisphenol AF, bisphenol BP, bisphenol B, bisphenol C, bisphenol E, bisphenol F, bisphenol G, bisphenol M, bisphenol S, bisphenol P, bisphenol Z.

[0257] 10. As described in any preceding embodiment, wherein the epoxy resin comprises or consists of an epoxy resin selected from the group consisting of epoxy resins produced by the reaction of epichlorohydrin and bisphenol A.

[0258] 11. As described in any of the preceding embodiments, wherein the at least one epoxy resin comprises or consists of an epoxy resin produced by the reaction of epichlorohydrin and bisphenol A and having a viscosity of less than 50,000 mPa.s, more preferably less than 20,000 mPa.s at 25°C when measured according to ASTM D-445.

[0259] 12. As described in any of the preceding embodiments, wherein the at least one liquid epoxy resin comprises a liquid reaction product of epichlorohydrin and bisphenol A, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445), and a functionality of 2.

[0260] 13. As described in any of the preceding embodiments, wherein the at least one liquid epoxy resin is used in an amount of 10-65 wt%, more preferably 35-60 wt%, and more particularly preferably 40-55 wt%, based on the total weight of the adhesive composition.

[0261] 14. As described in any of the preceding embodiments, wherein the at least one epoxy resin comprises or consists of an epoxy resin having a viscosity of less than 1,500,000 mPas at 25° C. when measured according to ASTM D-445, used in an amount of 10-65 wt %, more preferably 35-60 wt %, and more particularly preferably 40-55 wt %, based on the total weight of the adhesive composition.

[0262] 15. As described in any of the preceding embodiments, the at least one epoxy resin comprises or consists of an epoxy resin having a viscosity of less than 50,000 mPa.s, more preferably less than 20,000 mPa.s at 25°C when measured according to ASTM D-445, and is used in an amount of 10-65 wt%, more preferably 35-60 wt%, and more particularly preferably 40-55 wt%, based on the total weight of the adhesive composition.

[0263] 16. As described in any of the preceding embodiments, the at least one epoxy resin comprises or consists of an epoxy resin formed by the reaction of epichlorohydrin with bisphenol, in particular bisphenol A, bisphenol AP, bisphenol AF, bisphenol BP, bisphenol B, bisphenol C, bisphenol E, bisphenol F, bisphenol G, bisphenol M, bisphenol S, bisphenol P, bisphenol Z, and is used in an amount of 10-65 wt %, more preferably 35-60 wt %, and more preferably 40-55 wt %, based on the total weight of the adhesive composition.

[0264] 17. As described in any of the preceding embodiments, the at least one epoxy resin comprises or consists of an epoxy resin produced by the reaction of epichlorohydrin and bisphenol A, used in an amount of 10-65 wt%, more preferably 35-60 wt%, and more particularly preferably 40-55 wt%, based on the total weight of the adhesive composition.

[0265] 18. As described in any of the preceding embodiments, the at least one epoxy resin comprises or consists of an epoxy resin produced by the reaction of epichlorohydrin with bisphenol A and having a viscosity of less than 50,000 mPa.s, more preferably less than 20,000 mPa.s at 25°C when measured according to ASTM D-445, and is used in an amount of 30-65 wt%, more preferably 35-60 wt%, and more particularly preferably 40-55 wt%, based on the total weight of the adhesive composition.

[0266] 19. As described in any of the preceding embodiments, wherein the at least one liquid epoxy resin comprises a liquid reaction product of epichlorohydrin and bisphenol A, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445) and a functionality of 2, and is used in an amount of 10-65 wt %, more preferably 35-60 wt %, and more particularly preferably 40-55 wt %, based on the total weight of the adhesive composition.

[0267] 20. As described in any preceding embodiment, wherein the blowing agent is selected from physical blowing agents, which are low boiling point molecules or entrapped or encapsulated gases, and chemical blowing agents, which are molecules that decompose to release gases during curing.

[0268] 21. As described in any of the preceding embodiments, wherein the blowing agent is selected from expandable graphite, and gases (e.g., hydrocarbons such as butane, pentane) encapsulated in a polymer shell such as poly(acrylonitrile) and acrylate copolymers, and low boiling point molecules such as water, nitrogen, carbon dioxide, propane, butane and pentane.

[0269] 22. As described in any of the preceding embodiments, wherein the blowing agent is selected from:

[0270] 1. Isocyanate

[0271] 2. Azo compounds (e.g. azobisisobutyronitrile, diisopropyl azodicarboxylate, azodicarbonamide)

[0272] 3. Hydrazine derivatives [e.g. 4,4'-oxybis(benzenesulfonylhydrazide), p-toluenesulfonylhydrazide]

[0273] 4. Semicarbazide and sulfonyl semicarbazide [e.g. p-toluenesulfonyl semicarbazide, 4,4'-oxybis(benzenesulfonyl semicarbazide), p,p-oxybisbenzenesulfonyl hydrazide]

[0274] 5. N-nitroso compounds (e.g. dinitrosopentamethylenetetramine)

[0275] 6. Tetrazoles (e.g. 5-phenyltetrazole, 5-aminotetrazole)

[0276] 7. Poly(siloxane)

[0277] 8. Salts of carbonic acid and polycarboxylic acids (e.g. sodium bicarbonate)

[0278] 9. Peroxides (eg peroxycaproate, peroxydicarbonate).

[0279] 23. As described in any preceding embodiment, wherein the blowing agent is a physical blowing agent, more preferably a hydrocarbon gas encapsulated in a polymer, in particular propane, butane or pentane encapsulated in poly(acrylonitrile) and / or acrylate copolymers.

[0280] 24. As described in any preceding embodiment, the blowing agent is selected from propane, butane or pentane encapsulated in poly(acrylonitrile) and / or acrylate copolymers.

[0281] 25. As described in any of the preceding embodiments, the blowing agent is used at 0.25-2.35 wt%, more preferably 0.5-2.15 wt%, and more preferably 0.75-1.5 wt%, based on the total weight of the adhesive composition.

[0282] 26. As described in any of the preceding embodiments, the blowing agent is selected from physical blowing agents, which are low boiling point molecules or trapped or encapsulated gases, and chemical blowing agents, which are molecules that decompose to release gas during curing, and is used in an amount of 0.25-2.35 wt%, more preferably 0.5-2.15 wt%, and more particularly preferably 0.75-1.5 wt%, based on the total weight of the adhesive composition.

[0283] 27. As described in any of the preceding embodiments, the blowing agent is a physical blowing agent selected from expandable graphite, gases (e.g. hydrocarbons such as butane, pentane) encapsulated in a polymer shell such as poly(acrylonitrile) and acrylate copolymers, and low boiling point molecules such as water, nitrogen, carbon dioxide, propane, butane and pentane, used in an amount of 0.25-2.35 wt%, more preferably 0.5-2.15 wt%, and more particularly preferably 0.75-1.5 wt%, based on the total weight of the adhesive composition.

[0284] 28. As described in any of the preceding embodiments, wherein the blowing agent is selected from the following chemical blowing agents:

[0285] 1. Isocyanate

[0286] 2. Azo compounds (e.g. azobisisobutyronitrile, diisopropyl azodicarboxylate, azodicarbonamide)

[0287] 3. Hydrazine derivatives [e.g. 4,4'-oxybis(benzenesulfonylhydrazide), p-toluenesulfonylhydrazide]

[0288] 4. Semicarbazide and sulfonyl semicarbazide [e.g. p-toluenesulfonyl semicarbazide, 4,4'-oxybis(benzenesulfonyl semicarbazide), p,p-oxybisbenzenesulfonyl hydrazide]

[0289] 5. N-nitroso compounds (e.g. dinitrosopentamethylenetetramine)

[0290] 6. Tetrazoles (e.g. 5-phenyltetrazole, 5-aminotetrazole)

[0291] 7. Poly(siloxane)

[0292] 8. Salts of carbonic acid and polycarboxylic acids (e.g. sodium bicarbonate)

[0293] 9. Peroxides (e.g. peroxycaproate, peroxydicarbonate),

[0294] The amount used is 0.25-2.35 wt %, more preferably 0.5-2.15 wt %, and even more preferably 0.75-1.5 wt %, based on the total weight of the adhesive composition.

[0295] 29. As described in any of the preceding embodiments, the blowing agent is a hydrocarbon gas encapsulated in a polymer, in particular propane, butane or pentane encapsulated in poly(acrylonitrile) and / or acrylate copolymers, used in an amount of 0.25-2.35 wt%, more preferably 0.5-2.15 wt%, and more particularly preferably 0.75-1.5 wt%, based on the total weight of the adhesive composition.

[0296] 30. As described in any preceding embodiment, wherein the hardener is a latent hardener, which means a hardener that is activated when exposed to heat.

[0297] 31. As described in any preceding embodiment, the hardener is selected from dicyandiamide, hydrazide and anhydride hardeners.

[0298] 32. As described in any preceding embodiment, wherein the hardener is dicyandiamide.

[0299] 33. As described in any of the preceding embodiments, the hardener is selected from phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methyl-5-norbornene-2,3-dicarboxylic anhydride, alkenyl succinic anhydride (e.g., dodecenyl succinic anhydride) and trimellitic anhydride.

[0300] 34. As described in any preceding embodiment, wherein the hardener is selected from adipic acid dihydrazide, sebacic acid dihydrazide, dodecane dihydrazide, isophthalic acid dihydrazide and salicylic acid dihydrazide.

[0301] 35. As described in any preceding embodiment, the adhesive is a two-component adhesive in which the epoxy component and the hardener component are mixed immediately prior to use, and the hardener is selected from the group consisting of polyamines, substituted triazines, imidazoles, and polycarboxylic acids.

[0302] 36. As described in embodiment 35, the hardener is selected from aliphatic polyamines, alicyclic polyamines, aromatic polyamines, polyether-based polyamines, and polyethylene imine.

[0303] 37. As described in embodiment 35, the hardener is selected from diethylenetriamine, triethylenetetramine (TETA), triethylenediamine, tetraethylenepentamine, dipropylenediamine, diethylaminopropylamine, N-aminoethylpiperazine, menthanediamine, and isophoronediamine.

[0304] 38. As described in embodiment 35, wherein the hardener is selected from those based on poly(propylene oxide), such as those having the following structure:

[0305]

[0306]

[0307] 39. As described in any preceding embodiment, wherein the hardener is a latent hardener.

[0308] 40. As described in any preceding embodiment, wherein the hardener is dicyandiamide.

[0309] 41. As described in any of the preceding embodiments, the hardener is a latent hardener used at 0.5-8 wt%, more preferably 1-6 wt%, particularly preferably 3-5 wt%, based on the total weight of the adhesive composition.

[0310] 42. As described in any of the preceding embodiments, the hardener is selected from dicyandiamide, hydrazine and anhydride hardeners, and is used in an amount of 0.5-8 wt%, more preferably 1-6 wt%, and particularly preferably 3-5 wt%, based on the total weight of the adhesive composition.

[0311] 43. As described in any preceding embodiment, wherein the hardener is dicyandiamide, used at 0.5-8 wt%, more preferably 1-6 wt%, particularly preferably 3-5 wt%, based on the total weight of the adhesive composition.

[0312] 44. As described in any of the preceding embodiments, the hardener is a non-latent hardener selected from polyamines, polyamides, substituted triazines, imidazoles, polyols and polycarboxylic acids, and is used in an amount of 0.5-50 wt%, more preferably 20-50 wt%, and particularly preferably 30-50 wt%, based on the total weight of the mixed adhesive composition.

[0313] 45. As described in any of the preceding embodiments, the hardener is selected from alicyclic amines, aromatic amines, polyether-based polyamines, polyethylene imine, and is used in an amount of 0.5-50 wt%, more preferably 20-50 wt%, and particularly preferably 30-50 wt%, based on the total weight of the mixed adhesive composition.

[0314] 46. ​​As described in any of the preceding embodiments, the hardener is selected from diethylenetriamine, triethylenetetramine (TETA), triethylenediamine, tetraethylenepentamine, dipropylenediamine, diethylaminopropylamine, N-aminoethylpiperazine, menthanediamine, isophoronediamine, and is used in an amount of 0.5-50 wt%, more preferably 20-50 wt%, and particularly preferably 30-50 wt%, based on the total weight of the mixed adhesive composition.

[0315] 47. As described in any preceding embodiment, wherein the hardener is selected from those based on poly(propylene oxide), such as those having the following structure:

[0316]

[0317] The amount used is 0.5-50 wt %, more preferably 20-50 wt %, particularly preferably 30-50 wt %, based on the total weight of the mixed adhesive composition.

[0318] 48. As described in any preceding embodiment, the thermally conductive filler is selected from those having a thermal conductivity greater than 5 W / m°K, greater than 10 W / m°K, or greater than 15 W / m°K.

[0319] 49. As described in any of the preceding embodiments, the thermally conductive filler is selected from alumina, alumina trihydrate or aluminum hydroxide (ATH), silicon carbide, boron nitride, diamond, and graphite, and mixtures thereof, particularly preferred are aluminum hydroxide (ATH) and alumina, among which ATH is the most preferred.

[0320] 50. As described in any of the preceding embodiments, the thermally conductive filler is selected from a mixture of ATH and alumina, especially a mixture with a wt:wt ratio of ATH:alumina of 8-15.

[0321] 51. As described in any preceding embodiment, the thermally conductive filler has a broad particle size distribution characterized by a D90 / D50 ratio of 3 or about 3 or greater.

[0322] 52. As described in any preceding embodiment, wherein the thermally conductive filler is ATH or alumina having a broad particle size distribution characterized by a D90 / D50 ratio of 3 or about 3 or greater, most preferably ATH.

[0323] 53. As described in any preceding embodiment, the thermally conductive filler is selected from thermally conductive fillers having a bimodal particle size distribution.

[0324] 54. As described in any of the preceding embodiments, the thermally conductive filler has a D90 / D50 ratio of 3 or about 3 or greater, more preferably 5 or about 5 or greater, and more particularly preferably 9 or about 9 or greater.

[0325] 55. As described in any preceding embodiment, wherein the thermally conductive filler is selected from alumina and ATH with bimodal distribution and mixtures of these, in particular ATH.

[0326] 56. As described in any preceding embodiment, the thermally conductive filler is an ATH having a D90 / D50 of 3 or about 3 or greater, more preferably 5 or about 5 or greater, and particularly preferably 9 or about 9 or greater.

[0327] 57. As described in any preceding embodiment, wherein the thermally conductive filler is a bimodal aluminum hydroxide (ATH) having the following particle size distribution (by laser diffraction in deionized water containing a dispersing aid such as Na4P2O7 x 10H2O, preferably containing the dispersing aid at 1 g / l):

[0328] D 10 (micrometer) 0.5

[0329] D 50 (micrometer)8

[0330] D 90 (micrometers)80.

[0331] 58. As described in any preceding embodiment, the thermally conductive filler is present in the adhesive at a concentration of 10-55 wt%, more preferably 15-45 wt%, and even more preferably 20-42 wt%, based on the total weight of the final adhesive.

[0332] 59. As described in any preceding embodiment, the thermally conductive filler is aluminum hydroxide (ATH), used in a concentration of 10-55 wt%, more preferably 15-45 wt%, and more particularly preferably 20-42 wt%, based on the total weight of the adhesive.

[0333] 60. As described in any preceding embodiment, wherein the thermally conductive filler is aluminum hydroxide (ATH) having the following particle size distribution (by laser diffraction in deionized water containing a dispersing aid such as Na4P2O7 x 10H2O, preferably containing the dispersing aid at 1 g / l):

[0334] D 10 (micrometer) 0.5

[0335] D 50 (micrometer)8

[0336] D 90 (micrometer)80

[0337] The thermally conductive filler is used in a concentration of 10-55 wt %, more preferably 15-45 wt %, very particularly preferably 20-42 wt %, based on the total weight of the adhesive.

[0338] 61. As described in any preceding embodiment, the adhesive composition further comprises one or more toughening agents.

[0339] 62. As described in any preceding embodiment, the adhesive composition further comprises one or more toughening agents selected from polyurethane-based toughening agents, rubber-based toughening agents, and core-shell rubber toughening agents.

[0340] 63. As described in any preceding embodiment, wherein the at least one toughening agent is selected from those molecules with terminal functional groups that can react with the epoxy matrix during polymerization.

[0341] 64. As described in any of the preceding embodiments, the at least one toughening agent is selected from polyurethane-based toughening agents in which the terminal NCO groups are uncapped or capped (e.g., capped with phenol or polyphenol), polybutadiene-based toughening agents capped with amine or diol functional groups.

[0342] 65. As described in any preceding embodiment, wherein the at least one toughening agent is selected from polyurethane toughening agents, especially those in which the terminal NCO groups are capped with phenolic groups, especially cardanol.

[0343] 66. As described in any preceding embodiment, wherein the at least one toughening agent is prepared by reacting a polybutadiene diol, a polyether diol, and a diisocyanate such that the resulting molecule has terminal NCO groups.

[0344] 67. As described in any preceding embodiment, the at least one toughening agent is prepared by reacting polybutadiene diol, polyether diol and diisocyanate to obtain molecules with terminal NCO groups, followed by end-capping with phenol or polyphenol.

[0345] 68. As described in any preceding embodiment, the at least one toughening agent is prepared by reacting polybutadiene diol, polyether diol and diisocyanate to obtain molecules with terminal NCO groups, followed by end-capping with cardanol.

[0346] 69. As described in any preceding embodiment, the at least one toughening agent is used at 10-25 wt%, more preferably 12-18 wt%, based on the total weight of the adhesive.

[0347] 70. As described in any of the preceding embodiments, the toughening agent is selected from polyurethane-based toughening agents, rubber-based toughening agents and core-shell rubber toughening agents, and is used at 3-25 wt%, more preferably 12-18 wt%, based on the total weight of the adhesive.

[0348] 71. As described in any of the preceding embodiments, the at least one toughening agent is selected from those molecules with terminal functional groups that can react with the epoxy matrix during polymerization, used at 3-25 wt%, more preferably 12-18 wt%, based on the total weight of the adhesive.

[0349] 72. As described in any of the preceding embodiments, the at least one toughening agent is selected from polyurethane-based toughening agents in which the terminal NCO groups are uncapped or capped (e.g., capped with phenol or polyphenol), polybutadiene-based toughening agents capped with amine or diol functional groups, and is used in an amount of 3-25 wt%, more preferably 12-18 wt%, based on the total weight of the adhesive.

[0350] 73. As described in any of the preceding embodiments, the at least one toughening agent is selected from polyurethane toughening agents in which the terminal NCO groups are capped with phenolic groups, especially cardanol, and is used at 3-25 wt%, more preferably 12-18 wt%, based on the total weight of the adhesive.

[0351] 74. As described in any of the preceding embodiments, the at least one toughening agent is prepared by reacting polybutadiene diol, polyether diol and diisocyanate so that the resulting molecule has terminal NCO groups, and is used at 3-25 wt%, more preferably 12-18 wt%, based on the total weight of the adhesive.

[0352] 75. As described in any of the preceding embodiments, the at least one toughening agent is prepared by reacting polybutadiene diol, polyether diol and diisocyanate so that the resulting molecules have terminal NCO groups, followed by end-capping with cardanol, and is used in an amount of 3-25 wt%, more preferably 12-18 wt%, based on the total weight of the adhesive.

[0353] 76. As described in any preceding embodiment, the adhesive composition further comprises one or more silane adhesion promoters.

[0354] 77. As described in any of the preceding embodiments, wherein the adhesive composition further comprises one or more silane adhesion promoters having the general formula I:

[0355]

[0356] Where R 1 , R 2 and R 3 are independently selected from C1-C4-alkyl, R 2 is a divalent C2-C6-alkylene group, and W is a glycidyl group, an amino group or a mercapto group.

[0357] 78. As described in embodiment 77, wherein in formula I, W is glycidyl.

[0358] 79. As described in embodiment 77 or 78, wherein in formula I, R 1 , R 2 and R 3 is methyl and R 2 It is propylene.

[0359] 80. As described in embodiment 77, 78 or 79, wherein in formula I, R 1 , R 2 and R 3 is methyl, R 2 is propylene, and W is glycidyl.

[0360] 81. As described in any preceding embodiment, the adhesive composition comprises gamma-glycidylpropyltrimethoxysilane.

[0361] 82. As described in any preceding embodiment, the adhesive composition further comprises a silane adhesion promoter present in an amount of 0.05-1 wt%, more preferably 0.1-0.75 wt%, and even more preferably 0.2-0.4 wt%, based on the total weight of the adhesive composition.

[0362] 83. As described in embodiment 82, wherein the silane adhesion promoter has the general formula I:

[0363]

[0364] Where R 1 , R 2 and R 3 are independently selected from C1-C4-alkyl, R 2 W is a divalent C2-C6-alkylene group, and W is a glycidyl group, an amino group or a mercapto group, and the silane adhesion promoter is used in an amount of 0.05-1 wt %, more preferably 0.1-0.75 wt %, and more preferably 0.2-0.4 wt %, based on the total weight of the adhesive composition.

[0365] 84. As described in embodiment 82 or 83, wherein in formula I, W is glycidyl, and the adhesion promoter is used in an amount of 0.05-1 wt%, more preferably 0.1-0.75 wt%, and more preferably 0.2-0.4 wt%, based on the total weight of the adhesive composition.

[0366] 85. As described in embodiment 82, 83 or 84, wherein in formula I, R 1 , R 2 and R 3 is methyl and R 2 is propylene, and the adhesion promoter is used in an amount of 0.05-1 wt %, more preferably 0.1-0.75 wt %, and more particularly preferably 0.2-0.4 wt %, based on the total weight of the adhesive composition.

[0367] 86. As described in any one of embodiments 82-85, wherein in Formula I, R 1 , R 2 and R 3 is methyl, R2 W is a propylene group, and W is a glycidyl group, and the adhesion promoter is used in an amount of 0.05-1 wt %, more preferably 0.1-0.75 wt %, and more particularly preferably 0.2-0.4 wt %, based on the total weight of the adhesive composition.

[0368] 87. As described in any one of embodiments 82-95, the adhesive composition of the present invention contains γ-glycidylpropyltrimethoxysilane, which is used in an amount of 0.05-1 wt%, more preferably 0.1-0.75 wt%, and more preferably 0.2-0.4 wt%, based on the total weight of the adhesive composition.

[0369] 88. As described in any preceding embodiment, wherein the adhesive composition further comprises one or more epoxy polymerization catalysts.

[0370] 89. As described in any preceding embodiment, wherein the adhesive composition further comprises one or more epoxy polymerization catalysts selected from Lewis bases and Lewis acids.

[0371] 90. As described in any preceding embodiment, the adhesive composition further comprises one or more epoxy polymerization catalysts selected from tertiary amines and imidazoles.

[0372] 91. As described in any preceding embodiment, the adhesive composition further comprises one or more epoxy polymerization catalysts selected from 2,4,6-tris(dimethylaminomethyl)phenol, tetramethylguanidine, heptamethylisobiguanide, N,N-dimethylbenzylamine.

[0373] 92. As described in any preceding embodiment, the adhesive composition further comprises one or more epoxy polymerization catalysts, which are 2,4,6-tris(dimethylaminomethyl)phenol, especially 2,4,6-tris(dimethylaminomethyl)phenol on a novolac carrier.

[0374] 93. As described in any of the preceding embodiments, the adhesive composition further comprises one or more epoxy polymerization catalysts, which are used in an amount of 0.25-1.2 wt%, more preferably 0.5-1 wt%, based on the total weight of the adhesive composition.

[0375] 94. As described in any of the preceding embodiments, the adhesive composition further comprises one or more epoxy polymerization catalysts which are Lewis bases used at 0.25-1.2 wt%, more preferably 0.5-1 wt%, based on the total weight of the adhesive composition.

[0376] 95. As described in any of the preceding embodiments, the adhesive composition further comprises one or more epoxy polymerization catalysts selected from tertiary amines and imidazoles, used in an amount of 0.25-1.2 wt%, more preferably 0.5-1 wt%, based on the total weight of the adhesive composition.

[0377] 96. As described in any of the preceding embodiments, the adhesive composition further comprises one or more epoxy polymerization catalysts, which are tertiary amines, used in an amount of 0.25-1.2 wt%, more preferably 0.5-1 wt%, based on the total weight of the adhesive composition.

[0378] 97. As described in any of the preceding embodiments, the adhesive composition further comprises one or more epoxy polymerization catalysts selected from 2,4,6-tris(dimethylaminomethyl)phenol, tetramethylguanidine, heptamethylisobiguanide, N,N-dimethylbenzylamine, used in an amount of 0.25-1.2 wt%, more preferably 0.5-1 wt%, based on the total weight of the adhesive composition.

[0379] 98. As described in any of the preceding embodiments, the adhesive composition further comprises one or more epoxy polymerization catalysts, which are 2,4,6-tris(dimethylaminomethyl)phenol, especially 2,4,6-tris(dimethylaminomethyl)phenol on a phenolic lacquer carrier, used in an amount of 0.25-1.2 wt%, more preferably 0.5-1 wt%, based on the total weight of the adhesive composition.

[0380] 99. As described in any preceding embodiment, wherein the adhesive composition further comprises one or more thermoplastic polymers.

[0381] 100. As described in any preceding embodiment, the adhesive composition further comprises one or more thermoplastic polymers in the form of a powder, in particular a powder having an average particle size of less than 60 μm.

[0382] 101. As described in any preceding embodiment, the adhesive composition further comprises one or more thermoplastic polymers selected from polyamides, polyesters, and copolyetheresters, preferably in powder form.

[0383] 102. As described in any preceding embodiment, wherein the adhesive composition further comprises one or more thermoplastic polymers, the thermoplastic polymer being a polyamide, in particular a long chain polyamide.

[0384] 103. As described in any of the preceding embodiments, the adhesive composition further comprises one or more thermoplastic polymers selected from long-chain polyamides, preferably in powder form, made from diacids, diamines or lactams or amino-carboxylic acids having 6-12 carbon atoms.

[0385] 104. As described in any of the preceding embodiments, the adhesive composition further comprises one or more thermoplastic polymers selected from PA66, PA6, PA11, PA12, PA410, PA610, PA1010, PA612, PA1212, preferably in powder form.

[0386] 105. As described in any of the preceding embodiments, the adhesive composition further comprises one or more thermoplastic polymers, which are polyamides selected from the following: PA12, PA11, PA610, PA1010, PA612, PA1212, and mixtures of these, preferably in powder form, wherein particularly preferred is PA12, preferably in powder form.

[0387] 106. As described in any of the preceding embodiments, the adhesive composition further comprises one or more thermoplastic polymers, which are copolyetheresters preferably in powder form, in particular copolyetheresters comprising PBT hard segments and PTMEG soft segments, preferably in powder form.

[0388] 107. As described in any preceding embodiment, the adhesive composition further comprises one or more thermoplastic polymers, the thermoplastic polymer is a polyester preferably in powder form, especially PBT preferably in powder form.

[0389] 108. As described in any of the preceding embodiments, the adhesive composition further comprises one or more thermoplastic polymers, which are used in an amount of 5-30 wt%, more preferably 7-22 wt%, and particularly preferably 8-15 wt%, based on the total weight of the adhesive composition.

[0390] 109. As described in any of the preceding embodiments, the adhesive composition further comprises one or more thermoplastic polymers, which are in the form of powder, especially a powder with an average particle size of less than 60 μm, and are used in an amount of 5-30 wt%, more preferably 7-22 wt%, and particularly preferably 8-15 wt%, based on the total weight of the adhesive composition.

[0391] 110. As described in any of the preceding embodiments, the adhesive composition further comprises one or more thermoplastic polymers selected from polyamides, polyesters and copolyetheresters, preferably in powder form, used in an amount of 5-30 wt%, more preferably 7-22 wt%, and particularly preferably 8-15 wt%, based on the total weight of the adhesive composition.

[0392] 111. As described in any of the preceding embodiments, the adhesive composition further comprises one or more thermoplastic polymers, which are preferably polyamides in powder form, in particular polyamides made from diacids, diamines or lactams or amino-carboxylic acids having 6 to 12 carbon atoms, used in an amount of 5-30 wt%, more preferably 7-22 wt%, and particularly preferably 8-15 wt%, based on the total weight of the adhesive composition.

[0393] 112. As described in any of the preceding embodiments, the adhesive composition further comprises one or more thermoplastic polymers selected from PA66, PA6, PA11, PA12, PA410, PA610, PA1010, PA612, PA1212, preferably in powder form, and used in an amount of 5-30 wt%, more preferably 7-22 wt%, and particularly preferably 8-15 wt%, based on the total weight of the adhesive composition.

[0394] 113. As described in any of the preceding embodiments, the adhesive composition further comprises one or more thermoplastic polymers selected from PA12, PA11, PA610, PA1010, PA612, PA1212 and mixtures thereof, preferably in powder form, used in an amount of 5-30 wt%, more preferably 7-22 wt%, and particularly preferably 8-15 wt%, based on the total weight of the adhesive composition.

[0395] 114. As described in any of the preceding embodiments, the adhesive composition further comprises one or more thermoplastic polymers, which are selected from PA12, preferably in powder form, and are used in an amount of 5-30 wt%, more preferably 7-22 wt%, and particularly preferably 8-15 wt%, based on the total weight of the adhesive composition.

[0396] 115. As described in any of the preceding embodiments, the adhesive composition further comprises one or more thermoplastic polymers, which are copolyetheresters preferably in powder form, used in an amount of 5-30 wt%, more preferably 7-22 wt%, and particularly preferably 8-15 wt%, based on the total weight of the adhesive composition.

[0397] 116. As described in any of the preceding embodiments, the adhesive composition further comprises one or more thermoplastic polymers, which are copolyetheresters selected from those comprising PBT hard segments and PTMEG soft segments, preferably in powder form, and are used in an amount of 5-30 wt%, more preferably 7-22 wt%, and particularly preferably 8-15 wt%, based on the total weight of the adhesive composition.

[0398] 117. As described in any of the preceding embodiments, the adhesive composition further comprises one or more thermoplastic polymers, which are polyesters preferably in powder form, used in an amount of 5-30 wt%, more preferably 7-22 wt%, and particularly preferably 8-15 wt%, based on the total weight of the adhesive composition.

[0399] 118. As described in any of the preceding embodiments, the adhesive composition further comprises one or more thermoplastic polymers, which are preferably PBT in powder form, used in an amount of 5-30 wt%, more preferably 7-22 wt%, and particularly preferably 8-15 wt%, based on the total weight of the adhesive composition.

[0400] 119. As described in any preceding embodiment, wherein the adhesive composition exhibits a reduced 12 mm peak core temperature compared to an adhesive not comprising a thermally conductive filler and / or compared to an adhesive not comprising a thermoplastic polymer when measured using the method recited in the Examples.

[0401] 120. As described in any preceding embodiment, wherein the adhesive composition exhibits a 12 mm peak core temperature of 275°C or less, more preferably 260°C or less, when measured using the method recited in these examples.

[0402] 121. As described in any preceding embodiment, wherein the adhesive composition exhibits a percent expansion of 130% or greater.

[0403] 122. As described in any of the preceding embodiments, wherein the adhesive composition exhibits a 12 mm peak core temperature of 275°C or less, more preferably 260°C or less, and a percent expansion of 130% or greater when measured using the method recited in these examples.

[0404] Examples

[0405] The ingredients are listed in Table 1.

[0406]

[0407]

[0408]

[0409]

[0410] Preparation of adhesive

[0411] Using the amounts listed in Table 2, comparative samples and samples of the invention were prepared as follows:

[0412] Epoxy resins (Silquest A-187 and DER331) were weighed directly into a 300 mm long SpeedMixer TM The cup was then weighed with Worflex 7525. The cup was capped and placed in a Flacktek DAC600 SpeedMixer TM Mix at 2,300 rpm for one minute. TM Remove from the jar and allow to cool, then mix again using the same procedure. Next, weigh the red pigment, fumed silica, and aluminum trihydrate into the cup. Cover the cup and secure it with masking tape. Mix the contents in a Flacktek DAC600 SpeedMixer. TM Mix at 2,300 rpm for one minute, twice, allowing time for the composition to cool between mixing and maintaining a temperature of <65°C. Add CAB-O-SIL TS720 and mix the composition again using the above protocol. Finally, add epoxy polymerization catalyst (EPCAT 50), Dualite blowing agent and dicyandiamide. Cover the cup and tape it. Mix the composition three times using the above protocol. Between mixing, scrape the sample from the wall of the cup and mix it manually using a tongue depressor. Cover the final blend with a lid containing a small hole and then degas with a FlackTek Speed ​​Mixer model DAC 600VAC. To avoid boiling, increase the speed from 900 rpm to 1800 rpm.

[0413] The percent volume expansion and peak core temperature achieved for each adhesive at an oven temperature of 180°C at 15 mm adhesive layer thickness was determined and the results are summarized in Table 2.

[0414] Expansion rate

[0415] The percent expansion by volume is determined by hydrostatic weighing. For example, a small metal specimen is suspended on a balance and weighed in air and in a beaker with water. The adhesive is applied to the specimen and weighed again in air and in water. The adhesive is cured at 180° C. for 30 minutes and the resulting specimen with expanded adhesive is suspended on the bottom of a balance and reweighed in air and in water.

[0416] Calculate individual sample results using the following equation:

[0417] Expansion % = ((CC-UC) ÷ (UC-PC)) X 100%

[0418] in:

[0419] CC = the difference between the weight of the cured product of the sample in air and water.

[0420] UC = the difference between the uncured product of the sample in air and in water.

[0421] PC = the difference between the sample in air and in water.

[0422] Peak core temperature

[0423] The peak core temperature that each adhesive composition reaches during curing is monitored by placing a thermocouple in the center of the adhesive layer sandwiched between two metal plates. The sandwich sample is prepared by distributing the adhesive to a metal panel covered with Teflon paper (to prevent adhesion). The distributed adhesive is cut into a size of 100mmx25.4mmx 15mm or 100mm x25.4mmx 12mm. Metal spacers (height is 15mm or 12mm) are placed at each end of the resulting adhesive rectangular prism, and the metal panel covered with the second Teflon is added on the assembly. The assembly is fixed with four metal clips. Then the thermocouple is inserted into the center of the adhesive layer through the small hole (about 1mm diameter) in the center of the base plate. The second thermocouple is taped to the metal panel to monitor the temperature of the metal, and the third thermocouple is fixed to the oven rack on which the sample is placed to monitor the oven temperature. The final sandwich sample is placed in a preheated oven at 180°C for 30 minutes, and the peak core temperature of each sample is recorded.

[0424] Effect of adding thermoplastics

[0425] Inventive Example IE8 additionally comprises a thermoplastic in the form of a copolyetherester in the amount listed in Table 2. The thermoplastic is added together with the solid ingredients such as ATH.

[0426] Flexural properties of sandwich specimens

[0427] To evaluate flexural rigidity and strength, sandwich composites were prepared using 6061-T6 aluminum coupons (200 mm l x 25.4 mm w x 1.6 mm t) and 12 mm adhesive layers. The sandwich specimens were cured at 180°C for 30 minutes and tested in 3-point bending according to ASTM D7624 Procedure A using a support span of 120 mm and a test speed of 5 mm / min.

[0428]

[0429]

[0430] As shown in Table 2, Comparative Example 1, which is an expandable structural adhesive composition containing calcium carbonate, achieved a peak core temperature of 302° C. In contrast, when aluminum trihydrate (ATH) was used instead of calcium carbonate, a 52° C. to 63° C. reduction in peak core temperature was achieved. The addition of 2 wt % spherical alumina further reduced the core peak temperature by 7° C. relative to the same composition using only aluminum trihydrate.

[0431] Inventive example IE8 additionally contains a thermoplastic. This results in a significant reduction in the 12 mm peak core temperature compared to comparative example CE1 and inventive examples IE1, IE2 and IE3 without thermoplastic.

Claims

1. An expandable adhesive composition comprising: (A) at least one liquid epoxy resin; (B) at least one blowing agent; (C) at least one hardener; (D) At least one thermally conductive filler.

2. A method for bonding substrates, the method comprising the following steps: (1) Providing an expandable adhesive composition, which comprises: (A) at least one liquid epoxy resin; (B) at least one blowing agent; (C) at least one hardener; (D) at least one thermally conductive filler; (2) applying the expandable adhesive composition to the substrate; (3) expanding the expandable adhesive composition; and (4) Curing the expandable adhesive composition.

3. A bonded assembly comprising substrates bonded with an adhesive produced by expansion and curing of an expandable adhesive composition comprising: (A) at least one liquid epoxy resin; (B) at least one blowing agent; (C) at least one hardener; (D) At least one thermally conductive filler.

4. An expandable adhesive composition comprising: (A) at least one liquid epoxy resin; (B) at least one blowing agent; (C) at least one hardener; (D) at least one thermally conductive filler; (E) at least one thermoplastic polymer.

5. A method for bonding substrates, the method comprising the steps of: (1) Providing an expandable adhesive composition, which comprises: (A) at least one liquid epoxy resin; (B) at least one blowing agent; (C) at least one hardener; (D) at least one thermally conductive filler; (E) at least one thermoplastic polymer; (2) applying the expandable adhesive composition to the substrate; (3) expanding the expandable adhesive composition; and (4) Curing the expandable adhesive composition.

6. A bonded assembly comprising substrates bonded with an adhesive produced by expansion and curing of an expandable adhesive composition comprising: (A) at least one liquid epoxy resin; (B) at least one blowing agent; (C) at least one hardener; (D) at least one thermally conductive filler; (E) at least one thermoplastic polymer.

7. A method as claimed in any preceding claim, wherein: The liquid epoxy resins include all epoxy resins that are flowable at 25°C, preferably having a viscosity of less than 1,500,000 mPas at 25°C when measured according to ASTM D-445.

8. A method as claimed in any preceding claim, wherein: The at least one epoxy resin comprises or consists of the following epoxy resins, The epoxy resin has a viscosity of less than 50,000 mPa.s at 25°C, more preferably less than 20,000 mPa.s when measured according to ASTM D-445.

9. A method as claimed in any preceding claim, wherein: The epoxy resin comprises or consists of the following epoxy resins: The epoxy resin is selected from those formed by the reaction of epichlorohydrin with bisphenols, in particular bisphenol A, bisphenol AP, bisphenol AF, bisphenol BP, bisphenol B, bisphenol C, bisphenol E, bisphenol F, bisphenol G, bisphenol M, bisphenol S, bisphenol P, bisphenol Z.

10. A method as claimed in any preceding claim, wherein: The epoxy resin comprises or consists of an epoxy resin selected from epoxy resins produced by the reaction of epichlorohydrin and bisphenol A.

11. A method as claimed in any preceding claim, wherein: The at least one epoxy resin comprises or consists of an epoxy resin produced from the reaction of epichlorohydrin and bisphenol A and having a viscosity at 25°C of less than 50,000 mPa.s, more preferably less than 20,000 mPa.s when measured according to ASTM D-445.

12. A method as claimed in any preceding claim, wherein: The at least one liquid epoxy resin comprises a liquid reaction product of epichlorohydrin and bisphenol A, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445), and a functionality of 2.

13. A method as claimed in any preceding claim, wherein: The at least one liquid epoxy resin is used in an amount of 10 to 65 wt %, more preferably 35 to 60 wt %, very particularly preferably 40 to 55 wt %, based on the total weight of the adhesive composition.

14. A method as claimed in any preceding claim, wherein: The at least one epoxy resin comprises or consists of the following epoxy resins, The epoxy resin has a viscosity of less than 1,500,000 mPas at 25° C. when measured according to ASTM D-445 and is used at 10-65 wt %, more preferably 35-60 wt %, and even more preferably 40-55 wt %, based on the total weight of the adhesive composition.

15. A method as claimed in any preceding claim, wherein: The at least one epoxy resin comprises or consists of the following epoxy resins, The epoxy resin has a viscosity of less than 50,000 mPa.s, more preferably less than 20,000 mPa.s at 25°C when measured according to ASTM D-445, and is used at 10-65 wt%, more preferably 35-60 wt%, more particularly preferably 40-55 wt%, based on the total weight of the adhesive composition.

16. A method as claimed in any preceding claim, wherein: The at least one epoxy resin comprises or consists of an epoxy resin formed by the reaction of epichlorohydrin with bisphenol, in particular bisphenol A, bisphenol AP, bisphenol AF, bisphenol BP, bisphenol B, bisphenol C, bisphenol E, bisphenol F, bisphenol G, bisphenol M, bisphenol S, bisphenol P, bisphenol Z, and is used in an amount of 10-65 wt %, more preferably 35-60 wt %, and more preferably 40-55 wt %, based on the total weight of the adhesive composition.

17. A method as claimed in any preceding claim, wherein: The at least one epoxy resin comprises or consists of an epoxy resin produced by the reaction of epichlorohydrin and bisphenol A, used at 10-65 wt %, more preferably 35-60 wt %, and more particularly preferably 40-55 wt %, based on the total weight of the adhesive composition.

18. A method as claimed in any preceding claim, wherein: The at least one epoxy resin comprises or consists of an epoxy resin produced by the reaction of epichlorohydrin with bisphenol A and having a viscosity of less than 50,000 mPa.s, more preferably less than 20,000 mPa.s at 25° C. when measured according to ASTM D-445, and is used in an amount of 30-65 wt %, more preferably 35-60 wt %, and more particularly preferably 40-55 wt %, based on the total weight of the adhesive composition.

19. As claimed in any preceding claim, wherein the at least one liquid epoxy resin comprises a liquid reaction product of epichlorohydrin and bisphenol A, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445) and a functionality of 2, used in an amount of 10-65 wt %, more preferably 35-60 wt %, and more particularly preferably 40-55 wt %, based on the total weight of the adhesive composition.

20. A method as claimed in any preceding claim wherein the blowing agent is selected from physical blowing agents, which are low boiling point molecules or entrapped or encapsulated gases, and chemical blowing agents, which are molecules that decompose during curing to release gas.

21. A method as claimed in any preceding claim wherein the blowing agent is selected from expandable graphite, and gases (e.g. hydrocarbons such as butane, pentane) encapsulated in a polymer shell such as poly(acrylonitrile) and acrylate copolymers, and low boiling point molecules such as water, nitrogen, carbon dioxide, propane, butane and pentane.

22. A method according to any preceding claim, wherein the blowing agent is selected from:

1. Isocyanate 2. Azo compounds (e.g. azobisisobutyronitrile, diisopropyl azodicarboxylate, azodicarbonamide) 3. Hydrazine derivatives [e.g. 4,4-oxybis(benzenesulfonylhydrazide), p-toluenesulfonylhydrazide] 4. Semicarbazide and sulfonyl semicarbazide [e.g. p-toluenesulfonyl semicarbazide, 4,4-oxybis(benzenesulfonyl semicarbazide), p,p-oxybisbenzenesulfonyl hydrazide] 5. N-nitroso compounds (e.g. dinitrosopentamethylenetetramine) 6. Tetrazoles (e.g. 5-phenyltetrazole, 5-aminotetrazole) 7. Poly(siloxane) 8. Salts of carbonic acid and polycarboxylic acids (e.g. sodium bicarbonate) 9. Peroxides (eg peroxycaproate, peroxydicarbonate).

23. A method as claimed in any preceding claim, wherein: The blowing agent is a physical blowing agent, more preferably a hydrocarbon gas encapsulated in a polymer, especially propane, butane or pentane encapsulated in acrylonitrile.

24. A method as claimed in any preceding claim, wherein: The blowing agent is selected from propane, butane or pentane encapsulated in acrylonitrile.

25. A method according to any preceding claim, wherein the blowing agent is used in an amount of 0.25-2.35 wt%, more preferably 0.5-2.15 wt%, more particularly preferably 0.75-1.5 wt%, based on the total weight of the adhesive composition.

26. A method as claimed in any preceding claim, wherein the blowing agent is selected from physical blowing agents, which are low boiling point molecules or entrapped or encapsulated gases, and chemical blowing agents, which are molecules that decompose to release gases during curing, and is used in an amount of 0.25-2.35 wt%, more preferably 0.5-2.15 wt%, and more preferably 0.75-1.5 wt%, based on the total weight of the adhesive composition.

27. A method as claimed in any preceding claim, wherein the blowing agent is a physical blowing agent selected from expandable graphite, gases (e.g. hydrocarbons such as butane, pentane) encapsulated in a polymer shell such as poly(acrylonitrile) and acrylate copolymers, and low boiling point molecules such as water, nitrogen, carbon dioxide, propane, butane and pentane, used in an amount of 0.25-2.35 wt%, more preferably 0.5-2.15 wt%, and more particularly preferably 0.75-1.5 wt%, based on the total weight of the adhesive composition.

28. A method according to any preceding claim, wherein the blowing agent is selected from the group consisting of chemical blowing agents:

1. Isocyanate 2. Azo compounds (e.g. azobisisobutyronitrile, diisopropyl azodicarboxylate, azodicarbonamide) 3. Hydrazine derivatives [e.g. 4,4-oxybis(benzenesulfonylhydrazide), p-toluenesulfonylhydrazide] 4. Semicarbazide and sulfonyl semicarbazide [e.g. p-toluenesulfonyl semicarbazide, 4,4-oxybis(benzenesulfonyl semicarbazide), p,p-oxybisbenzenesulfonyl hydrazide] 5. N-nitroso compounds (e.g. dinitrosopentamethylenetetramine) 6. Tetrazoles (e.g. 5-phenyltetrazole, 5-aminotetrazole) 7. Poly(siloxane) 8. Salts of carbonic acid and polycarboxylic acids (e.g. sodium bicarbonate) 9. Peroxides (e.g. peroxycaproate, peroxydicarbonate), The amount used is 0.25-2.35 wt %, more preferably 0.5-2.15 wt %, and even more preferably 0.75-1.5 wt %, based on the total weight of the adhesive composition.

29. A method as claimed in any preceding claim, wherein: The blowing agent is a hydrocarbon gas encapsulated in a polymer, in particular propane, butane or pentane encapsulated in acrylonitrile, used at 0.25-2.35 wt%, more preferably 0.5-2.15 wt%, more particularly preferably 0.75-1.5 wt%, based on the total weight of the adhesive composition.

30. A method as claimed in any preceding claim, wherein: The hardener is a latent hardener, which means a hardener that is activated when exposed to heat.

31. A method as claimed in any preceding claim, wherein: The hardener is selected from dicyandiamide, hydrazide and anhydride hardeners.

32. A method as claimed in any preceding claim, wherein: The hardener is dicyandiamide.

33. A method as claimed in any preceding claim, wherein: The hardener is selected from phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methyl-5-norbornene-2,3-dicarboxylic anhydride, alkenyl succinic anhydride (eg, dodecenyl succinic anhydride), and trimellitic anhydride.

34. A method as claimed in any preceding claim, wherein: The hardener is selected from adipic acid dihydrazide, sebacic acid dihydrazide, dodecane dihydrazide, isophthalic acid dihydrazide and salicylic acid dihydrazide.

35. A method as claimed in any preceding claim, wherein: The adhesive is a two-component adhesive in which the epoxy component and the hardener component are mixed immediately prior to use, and the hardener is selected from the group consisting of polyamines, polyamides, substituted triazines, imidazoles, polyols and polycarboxylic acids.

36. As claimed in claim 35, wherein The hardener is selected from aliphatic polyamines, alicyclic polyamines, aromatic polyamines, polyether-based polyamines, and polyethylene imine.

37. As claimed in claim 35, wherein The hardener is selected from diethylenetriamine, triethylenetetramine (TETA), triethylenediamine, tetraethylenepentamine, dipropylenediamine, diethylaminopropylamine, N-aminoethylpiperazine, menthanediamine, isophoronediamine.

38. As claimed in claim 35, wherein The hardener is selected from those based on poly(propylene oxide), such as those having the following structure:

39. Any preceding claim, wherein: The hardener is a latent hardener.

40. Any preceding claim, wherein: The hardener is dicyandiamide.

41. Any preceding claim, wherein: The hardener is a latent hardener, and is used in an amount of 0.5-8 wt %, more preferably 1-6 wt %, particularly preferably 3-5 wt %, based on the total weight of the adhesive composition.

42. Any preceding claim, wherein: The hardener is selected from dicyandiamide, hydrazine and anhydride hardeners, and is used at 0.5-8 wt %, more preferably 1-6 wt %, particularly preferably 3-5 wt %, based on the total weight of the adhesive composition.

43. Any preceding claim, wherein: The hardener is dicyandiamide, which is used in an amount of 0.5-8 wt %, more preferably 1-6 wt %, particularly preferably 3-5 wt %, based on the total weight of the adhesive composition.

44. Any preceding claim, wherein: The hardener is a non-latent hardener selected from polyamines, polyamides, substituted triazines, imidazoles, polyols and polycarboxylic acids, and is used at 0.5-50 wt %, more preferably 20-50 wt %, particularly preferably 30-50 wt % based on the total weight of the mixed adhesive composition.

45. Any preceding claim, wherein: The hardener is selected from alicyclic amines, aromatic amines, polyether-based polyamines, polyethylene imine, and is used in an amount of 0.5-50 wt %, more preferably 20-50 wt %, particularly preferably 30-50 wt %, based on the total weight of the adhesive composition.

46. ​​Any preceding claim, wherein: The hardener is selected from diethylenetriamine, triethylenetetramine (TETA), triethylenediamine, tetraethylenepentamine, dipropylenediamine, diethylaminopropylamine, N-aminoethylpiperazine, menthanediamine, isophoronediamine, and is used in an amount of 0.5-50 wt %, more preferably 20-50 wt %, and particularly preferably 30-50 wt %, based on the total weight of the adhesive composition.

47. Any preceding claim, wherein: The hardener is selected from those based on poly(propylene oxide), such as those having the following structure: The amount of the polyol used is 0.5-50 wt %, more preferably 20-50 wt %, particularly preferably 30-50 wt %, based on the total weight of the adhesive composition.

48. Any preceding claim, wherein: The thermally conductive filler is selected from those having a thermal conductivity greater than 5 W / m°K, greater than 10 W / m°K, or greater than 15 W / m°K.

49. Any preceding claim, wherein: The thermally conductive filler is selected from alumina, alumina trihydrate or aluminum hydroxide (ATH), silicon carbide, boron nitride, diamond, and graphite, and mixtures thereof, particularly preferably aluminum hydroxide (ATH) and alumina, wherein ATH is most preferred.

50. Any preceding claim, wherein: The thermally conductive filler is selected from a mixture of ATH and alumina, in particular a mixture with a wt:wt ratio of ATH:alumina of 8-15.

51. Any preceding claim, wherein: The thermally conductive filler has a broad particle size distribution characterized by a D90 / D50 ratio of 3 or about 3 or greater.

52. Any preceding claim, wherein: The thermally conductive filler is ATH or alumina having a broad particle size distribution characterized by a D90 / D50 ratio of 3 or about 3 or greater, most preferably ATH.

53. Any preceding claim, wherein: The thermally conductive filler is selected from thermally conductive fillers having a bimodal particle size distribution.

54. Any preceding claim, wherein: The thermally conductive filler has a D90 / D50 ratio of 3 or about 3 or greater, more preferably 5 or about 5 or greater, and even more preferably 9 or about 9 or greater.

55. Any preceding claim, wherein: The thermally conductive filler is selected from alumina and ATH with bimodal distribution and mixtures of these, in particular ATH.

56. Any preceding claim, wherein: The thermally conductive filler is an ATH having a D90 / D50 of 3 or about 3 or more, more preferably 5 or about 5 or more, and particularly preferably 9 or about 9 or more.

57. Any preceding claim, wherein: The thermally conductive filler is a bimodal aluminum hydroxide (ATH) having the following particle size distribution (by laser diffraction in deionized water containing a dispersing aid such as Na4P2O7 x 10H2O, preferably containing the dispersing aid at 1 g / l): D 10 (micrometer) 0.5 D 50 (micrometer)8 D 90 (micrometers)80.

58. Any preceding claim, wherein: The thermally conductive filler is present in the adhesive in a concentration of 10-55 wt %, more preferably 15-45 wt %, very particularly preferably 20-42 wt %, based on the total weight of the finished adhesive.

59. Any preceding claim, wherein: The thermally conductive filler is aluminum hydroxide (ATH), used in a concentration of 10-55 wt %, more preferably 15-45 wt %, and most preferably 20-42 wt %, based on the total weight of the adhesive.

60. Any preceding claim, wherein: The thermally conductive filler is aluminum hydroxide (ATH) having the following particle size distribution (by laser diffraction in deionized water containing a dispersing aid such as Na4P2O7 x 10H2O, preferably containing the dispersing aid at 1 g / l): D 10 (micrometer) 0.5 D 50 (micrometer)8 D 90 (micrometer)80 The thermally conductive filler is used in a concentration of 10-55 wt %, more preferably 15-45 wt %, very particularly preferably 20-42 wt %, based on the total weight of the adhesive.

61. Any preceding claim, wherein: The adhesive composition additionally comprises one or more toughening agents.

62. Any preceding claim, wherein: The adhesive composition further comprises one or more toughening agents selected from polyurethane-based toughening agents, rubber-based toughening agents, and core-shell rubber toughening agents.

63. Any preceding claim, wherein: The at least one toughening agent is selected from those molecules carrying terminal functional groups that can react with the epoxy matrix during polymerization.

64. Any preceding claim, wherein: The at least one toughening agent is selected from polyurethane-based toughening agents in which the terminal NCO groups are uncapped or capped (eg, with phenol or polyphenol), polybutadiene-based toughening agents capped with amine or diol functional groups.

65. Any preceding claim, wherein: The at least one toughening agent is selected from polyurethane toughening agents, in particular those in which the terminal NCO groups are capped with phenolic groups, in particular cardanol.

66. Any preceding claim, wherein: The at least one toughening agent is prepared by reacting a polybutadiene diol, a polyether diol, and a diisocyanate such that the resulting molecule has terminal NCO groups.

67. Any preceding claim, wherein: The at least one toughening agent is prepared by reacting polybutadiene diol, polyether diol and diisocyanate so that the resulting molecule has terminal NCO groups, followed by end-capping with phenol or polyphenol.

68. Any preceding claim, wherein: The at least one toughening agent is prepared by reacting polybutadiene diol, polyether diol and diisocyanate so that the resulting molecule has a terminal NCO group, followed by end-capping with cardanol.

69. Any preceding claim, wherein: The at least one toughening agent is used at 3-25 wt%, more preferably 12-18 wt%, based on the total weight of the adhesive.

70. Any preceding claim, wherein: The toughening agent is selected from polyurethane-based toughening agents, rubber-based toughening agents and core-shell rubber toughening agents, and is used at 3-25 wt%, more preferably 12-18 wt%, based on the total weight of the adhesive.

71. Any preceding claim, wherein: The at least one toughening agent is selected from those molecules with terminal functional groups that can react with the epoxy matrix during polymerization and is used at 3-25 wt%, more preferably 12-18 wt%, based on the total weight of the adhesive.

72. Any preceding claim, wherein: The at least one toughening agent is selected from polyurethane-based toughening agents in which the terminal NCO group is uncapped or capped (e.g., capped with phenol or polyphenol), polybutadiene-based toughening agents capped with amine or diol functional groups, and is used in an amount of 3-25 wt%, more preferably 12-18 wt%, based on the total weight of the adhesive.

73. Any preceding claim, wherein: The at least one toughening agent is selected from polyurethane toughening agents in which the terminal NCO groups are capped with phenolic groups, especially cardanol, and is used at 3-25 wt%, more preferably 12-18 wt%, based on the total weight of the adhesive.

74. Any preceding claim, wherein: The at least one toughening agent is prepared by reacting polybutadiene diol, polyether diol and diisocyanate so that the resulting molecule carries terminal NCO groups and is used at 3-25 wt%, more preferably 12-18 wt%, based on the total weight of the adhesive.

75. Any preceding claim, wherein: The at least one toughening agent is prepared by reacting polybutadiene diol, polyether diol and diisocyanate to give a molecule with terminal NCO groups, followed by end-capping with cardanol, and is used at 3-25 wt%, more preferably 12-18 wt%, based on the total weight of the adhesive.

76. Any preceding claim, wherein: The adhesive composition additionally comprises one or more silane adhesion promoters.

77. Any preceding claim, wherein: The adhesive composition further comprises one or more silane adhesion promoters having the general formula I: Where R 1 , R 2 and R 3 are independently selected from C1-C4-alkyl, R 2 is a divalent C2-C6-alkylene group, and W is a glycidyl group, an amino group or a mercapto group.

78. As claimed in claim 77, wherein In Formula I, W is glycidyl.

79. The method of claim 77 or 78, wherein: In Formula I, R 1 , R 2 and R 3 is methyl and R 2 It is propylene.

80. Claim 77, 78 or 79, wherein In Formula I, R 1 , R 2 and R 3 is methyl, R 2 is propylene, and W is glycidyl.

81. Any preceding claim, wherein: The adhesive composition includes γ-glycidylpropyltrimethoxysilane.

82. Any preceding claim, wherein: The adhesive composition further comprises a silane adhesion promoter, which is present in an amount of 0.05 to 1 wt %, more preferably 0.1 to 0.75 wt %, very particularly preferably 0.2 to 0.4 wt %, based on the total weight of the adhesive composition.

83. As claimed in claim 82, wherein The silane adhesion promoter has the general formula I: Where R 1 , R 2 and R 3 are independently selected from C1-C4-alkyl, R 2 W is a divalent C2-C6-alkylene group, and W is a glycidyl group, an amino group or a mercapto group, and the silane adhesion promoter is used in an amount of 0.05-1 wt %, more preferably 0.1-0.75 wt %, and more preferably 0.2-0.4 wt %, based on the total weight of the adhesive composition.

84. As claimed in claim 82 or 83, wherein In formula I, W is a glycidyl group, and the adhesion promoter is used in an amount of 0.05-1 wt %, more preferably 0.1-0.75 wt %, and more particularly preferably 0.2-0.4 wt %, based on the total weight of the adhesive composition.

85. Claim 82, 83 or 84, wherein In Formula I, R 1 , R 2 and R 3 is methyl and R 2 is propylene, and the adhesion promoter is used in an amount of 0.05-1 wt %, more preferably 0.1-0.75 wt %, and more particularly preferably 0.2-0.4 wt %, based on the total weight of the adhesive composition.

86. Any one of claims 82-85, wherein In Formula I, R 1 , R 2 and R 3 is methyl, R 2 is a propylene group, and W is a glycidyl group, and the adhesion promoter is used in an amount of 0.05-1 wt %, more preferably 0.1-0.75 wt %, and more particularly preferably 0.2-0.4 wt %, based on the total weight of the adhesive composition.

87. Any one of claims 82-85, wherein The adhesive composition of the present invention contains γ-glycidylpropyltrimethoxysilane, which is used in an amount of 0.05-1 wt %, more preferably 0.1-0.75 wt %, and more particularly preferably 0.2-0.4 wt %, based on the total weight of the adhesive composition.

88. Any preceding claim, wherein: The adhesive composition additionally comprises one or more epoxy polymerization catalysts.

89. Any preceding claim, wherein: The adhesive composition further comprises one or more epoxy polymerization catalysts selected from Lewis bases and Lewis acids.

90. Any preceding claim, wherein: The adhesive composition further comprises one or more epoxy polymerization catalysts selected from tertiary amines and imidazoles.

91. Any preceding claim, wherein: The adhesive composition further comprises one or more epoxy polymerization catalysts selected from 2,4,6-tris(dimethylaminomethyl)phenol, tetramethylguanidine, heptamethylisobiguanide, and N,N-dimethylbenzylamine.

92. Any preceding claim, wherein: The adhesive composition additionally comprises one or more epoxide polymerization catalysts which are 2,4,6-tris(dimethylaminomethyl)phenol, particularly 2,4,6-tris(dimethylaminomethyl)phenol on a novolac carrier.

93. Any preceding claim, wherein: The adhesive composition further comprises one or more epoxy polymerization catalysts, which are used at 0.25-1.2 wt%, more preferably 0.5-1 wt%, based on the total weight of the adhesive composition.

94. As claimed in any preceding claim, wherein The adhesive composition further comprises one or more epoxy polymerization catalysts, which are Lewis bases, used at 0.25-1.2 wt%, more preferably 0.5-1 wt%, based on the total weight of the adhesive composition.

95. Any preceding claim, wherein: The adhesive composition further comprises one or more epoxy polymerization catalysts selected from tertiary amines and imidazoles, used at 0.25-1.2 wt%, more preferably 0.5-1 wt%, based on the total weight of the adhesive composition.

96. Any preceding claim, wherein: The adhesive composition further comprises one or more epoxy polymerization catalysts, which are tertiary amines, used at 0.25-1.2 wt%, more preferably 0.5-1 wt%, based on the total weight of the adhesive composition.

97. Any preceding claim, wherein: The adhesive composition further comprises one or more epoxy polymerization catalysts selected from 2,4,6-tris(dimethylaminomethyl)phenol, tetramethylguanidine, heptamethylisobiguanide, N,N-dimethylbenzylamine, used in an amount of 0.25-1.2 wt %, more preferably 0.5-1 wt %, based on the total weight of the adhesive composition.

98. Any preceding claim, wherein: The adhesive composition further comprises one or more epoxide polymerization catalysts which are 2,4,6-tris(dimethylaminomethyl)phenol, particularly 2,4,6-tris(dimethylaminomethyl)phenol on a novolac carrier, used at 0.25-1.2 wt%, more preferably 0.5-1 wt%, based on the total weight of the adhesive composition.

99. Any preceding claim, wherein: The adhesive composition additionally comprises one or more thermoplastic polymers.

100. Any preceding claim, wherein: The adhesive composition further comprises one or more thermoplastic polymers in the form of a powder, in particular a powder having an average particle size of less than 60 μm.

101. Any preceding claim, wherein: The adhesive composition further comprises one or more thermoplastic polymers selected from polyamides, polyesters and copolyetheresters, preferably in powder form.

102. Any preceding claim, wherein: The adhesive composition further comprises one or more thermoplastic polymers, which are polyamides, in particular long-chain polyamides.

103. Any preceding claim, wherein: The adhesive composition further comprises one or more thermoplastic polymers selected from long-chain polyamides, preferably in powder form, made from diacids, diamines or lactams or amino-carboxylic acids having 6 to 12 carbon atoms.

104. Any preceding claim, wherein: The adhesive composition further comprises one or more thermoplastic polymers selected from PA66, PA6, PA11, PA12, PA410, PA610, PA1010, PA612, PA1212, preferably in powder form.

105. Any preceding claim, wherein: The adhesive composition further comprises one or more thermoplastic polymers which are polyamides selected from the group consisting of PA12, PA11, PA610, PA1010, PA612, PA1212, preferably in powder form, and mixtures of these, wherein particular preference is given to PA12, preferably in powder form.

106. Any preceding claim, wherein: The adhesive composition further comprises one or more thermoplastic polymers, which are copolyetheresters, preferably in powder form, in particular copolyetheresters comprising PBT hard segments and PTMEG soft segments, preferably in powder form.

107. Any preceding claim, wherein: The adhesive composition further comprises one or more thermoplastic polymers, which are polyesters, preferably in powder form, in particular PBT, preferably in powder form.

108. Any preceding claim, wherein: The adhesive composition further comprises one or more thermoplastic polymers, which are used in an amount of 5-30 wt %, more preferably 7-22 wt %, particularly preferably 8-15 wt %, based on the total weight of the adhesive composition.

109. Any preceding claim, wherein: The adhesive composition further comprises one or more thermoplastic polymers, which are in the form of a powder, especially a powder with an average particle size of less than 60 μm, and are used in an amount of 5-30 wt%, more preferably 7-22 wt%, particularly preferably 8-15 wt%, based on the total weight of the adhesive composition.

110. Any preceding claim, wherein: The adhesive composition further comprises one or more thermoplastic polymers selected from polyamides, polyesters and copolyetheresters, preferably in powder form, used in 5-30 wt %, more preferably 7-22 wt %, particularly preferably 8-15 wt %, based on the total weight of the adhesive composition.

111. Any preceding claim, wherein: The adhesive composition further comprises one or more thermoplastic polymers, which are polyamides, preferably in powder form, in particular polyamides made from diacids, diamines or lactams or amino-carboxylic acids having 6 to 12 carbon atoms, used in an amount of 5 to 30 wt %, more preferably 7 to 22 wt %, particularly preferably 8 to 15 wt %, based on the total weight of the adhesive composition.

112. As claimed in any preceding claim, wherein: The adhesive composition further comprises one or more thermoplastic polymers selected from PA66, PA6, PA11, PA12, PA410, PA610, PA1010, PA612, PA1212, preferably in powder form, used in an amount of 5-30 wt%, more preferably 7-22 wt%, particularly preferably 8-15 wt%, based on the total weight of the adhesive composition.

113. Any preceding claim, wherein: The adhesive composition further comprises one or more thermoplastic polymers selected from PA12, PA11, PA610, PA1010, PA612, PA1212 and mixtures of these, preferably in powder form, used in an amount of 5-30 wt%, more preferably 7-22 wt%, particularly preferably 8-15 wt%, based on the total weight of the adhesive composition.

114. Any preceding claim, wherein: The adhesive composition further comprises one or more thermoplastic polymers selected from PA12, preferably in powder form, used at 5-30 wt%, more preferably 7-22 wt%, particularly preferably 8-15 wt%, based on the total weight of the adhesive composition.

115. Any preceding claim, wherein: The adhesive composition further comprises one or more thermoplastic polymers, which are copolyetheresters, preferably in powder form, used in an amount of 5-30 wt %, more preferably 7-22 wt %, particularly preferably 8-15 wt %, based on the total weight of the adhesive composition.

116. Any preceding claim, wherein: The adhesive composition further comprises one or more thermoplastic polymers, which are copolyetheresters selected from those comprising PBT hard segments and PTMEG soft segments, preferably in powder form, used in an amount of 5-30 wt%, more preferably 7-22 wt%, particularly preferably 8-15 wt%, based on the total weight of the adhesive composition.

117. Any preceding claim, wherein: The adhesive composition further comprises one or more thermoplastic polymers, which are polyesters, preferably in powder form, used in an amount of 5-30 wt %, more preferably 7-22 wt %, particularly preferably 8-15 wt %, based on the total weight of the adhesive composition.

118. Any preceding claim, wherein: The adhesive composition further comprises one or more thermoplastic polymers, which are preferably PBT in powder form, used at 5-30 wt%, more preferably 7-22 wt%, particularly preferably 8-15 wt%, based on the total weight of the adhesive composition.

119. Any preceding claim, wherein: The adhesive composition exhibits a reduced 12 mm peak core temperature as compared to an adhesive not including a thermally conductive filler and / or as compared to an adhesive not including a thermoplastic polymer, when measured using the method set forth in the Examples.

120. Any preceding claim, wherein: The adhesive composition exhibits a 12 mm peak core temperature of 275°C or less, more preferably 260°C or less, when measured using the method set forth in the Examples.

121. Any preceding claim, wherein: The adhesive composition exhibits an expansion percentage of 130% or more.

122. As claimed in any preceding claim, wherein: When measured using the method listed in the examples, the adhesive composition exhibits a 12 mm peak core temperature of 275° C. or less, more preferably 260° C. or less, and a percent expansion of 130% or more.